Printed matter and method for producing printed matter

JP7631980B2Active Publication Date: 2025-02-19FUJIFILM BUSINESS INNOVATION CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021055131
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-29
Publication Date
2025-02-19
Estimated Expiration
2041-03-29

AI Technical Summary

Benefits of technology

【0007】 <1>に係る発明によれば、画像部と圧力相転移性層とが形成された面を圧着面として、記録媒体を折り重ねて圧着され、又は、画像部と圧力相転移性層とが形成された面を圧着面として、記録媒体と別の記録媒体とを重ねて圧着された印刷物において、記録媒体の圧着面における、画像部上に形成された圧力相転移性層の平均厚さと非画像部に形成された圧力相転移性層の平均厚さとが同じである場合に比べ、圧着面の圧着力のバラツキが低減された印刷物が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631980000005
    Figure 0007631980000005
  • Figure 0007631980000006
    Figure 0007631980000006
  • Figure 0007631980000007
    Figure 0007631980000007
Patent Text Reader

Abstract

To provide a printed material in which variations in the crimping force of crimp surfaces are reduced.SOLUTION: There is provided a printed material in which a recording medium is folded and crimped with surfaces where an image portion and a pressure phase transition layer are formed as crimp surfaces or a recording medium and another recording medium are superimposed on each other and crimped with surfaces where the image portion and the pressure phase transition layer are formed as crimp surfaces. The average thickness of the pressure phase transition layer formed on the image portion on the crimp surface of the recording medium is larger than the average thickness of the pressure phase transition layer formed in a non-image portion.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a printed matter and a method for producing a printed matter. [Background technology]

[0002] Patent Document 1 discloses a powder fixing agent that is "configured so as to be applicable to a paper surface through the processes of development, transfer and fixing by electrophotography, has a basic structure of a cyclic polyolefin resin, contains 40% or more of the cyclic polyolefin resin and contains 30% or less of a thermoplastic elastomer."

[0003] Patent document 2 discloses "an apparatus for producing a laminated print that completes a laminated print by laminating the laminated surfaces of sheet-like printing media for use in a laminated print on which variable information has been printed with toner, the apparatus comprising at least a fixer application means for post-applying a powder fixer to a predetermined surface of the sheet-like printing medium on which the variable information has been printed with toner, and a print area setting means for setting the print area for printing the variable information to an area smaller than the application area of ​​the powder fixer applied by the fixer application means." [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-170659 A [Patent Document 2] JP 2008-173831 A Summary of the Invention [Problem to be solved by the invention]

[0005] The object of the present invention is to provide a printed matter in which a recording medium is folded and pressed onto the surface on which an image area and a pressure phase transition layer are formed, as the pressing surface, or a recording medium is stacked on top of another recording medium and pressed onto the surface on which an image area and a pressure phase transition layer are formed, as the pressing surface, in which the variation in the pressing force of the pressing surface is reduced compared to when the average thickness of the pressure phase transition layer formed on the image area and the average thickness of the pressure phase transition layer formed on the non-image area are the same on the pressing surface of the recording medium. [Means for solving the problem]

[0006] Specific means for solving the above problems include the following aspects. <1> The recording medium is folded and pressed onto the surface on which the image area and the pressure phase transition layer are formed, or the recording medium and another recording medium are stacked and pressed onto the surface on which the image area and the pressure phase transition layer are formed, and the surface on which the image area and the pressure phase transition layer are formed is used as a pressing surface. an average thickness of the pressure-induced phase change layer formed on the image area of ​​the pressure-bonding surface of the recording medium is greater than an average thickness of the pressure-induced phase change layer formed on the non-image area; printed matter. <2> The thickness of the pressure phase transition layer formed on the image area increases as the thickness of the image area increases. <1> The printed matter described in. <3> the average thickness of the pressure phase transition layer formed on the image area is 0.5 μm or more and 5.0 μm or less; The average thickness of the image area is more than 0 μm and 5.0 μm or less, In addition, when the thickness BR of the image portion is 0.5 μm or less, the following formulae (1) to (3) are satisfied: <2> The printed matter described in. Formula (1): AR=X1×BR+Y1 (Formula 1) Formula (2): 2≦X1≦10 Formula (3): 0.5≦Y1≦2 (In formula (1), AR represents the thickness (μm) of the pressure-induced phase transition layer formed on the image area, and BR represents the thickness (μm) of the image area. However, the thicknesses represented by AR and BR are the thickness of the pressure-induced phase transition layer directly above the image area and the thickness of the image area directly below the pressure-induced phase transition layer for which the thickness was calculated.) <4> The coverage of the pressure phase transition layer formed on the image area is 60% or more and 100% or less. <1> ~ <3> 13. The printed matter according to any one of claims 1 to 12. <5> The coverage of the pressure phase transition layer formed in the non-image area is 10% or more and 60% or less. <4> The printed matter described in. <6> The image portion is a toner image portion. <1> ~ <5> 13. The printed matter according to any one of claims 1 to 12. <7> The pressure phase transition layer includes a styrene-based resin containing styrene and other vinyl monomers as polymerization components, and a (meth)acrylic acid ester-based resin containing at least two (meth)acrylic acid esters as polymerization components, the mass ratio of the (meth)acrylic acid esters being 90 mass% or more of the total polymerization components, and has at least two glass transition temperatures, and the difference between the lowest glass transition temperature and the highest glass transition temperature among the glass transition temperatures exhibited by the pressure phase transition layer is 30° C. or more. <1> ~ <6> 13. The printed matter according to any one of claims 1 to 12. <8> The mass ratio of styrene in the total polymerization components of the styrene-based resin is 60 mass % or more and 95 mass % or less. <7> The printed matter described in. <9> The (meth)acrylic acid ester resin contains at least two (meth)acrylic acid esters as polymerization components, and the mass ratio of the two (meth)acrylic acid esters having the largest mass ratios is 80:20 to 20:80. <7> or <8> The printed matter described in. <10> a pressure-induced phase transition particle applying step of applying pressure-induced phase transition particles onto the recording medium on which the image area is formed; a fixing step of fixing at least the pressure-induced phase change particles onto the recording medium to form a pressure-induced phase change layer; a pressure bonding step of folding the recording medium and pressure bonding the recording medium with the surface on which the image portion and the pressure phase transition layer are formed being a pressure bonding surface, or of stacking the recording medium and another recording medium and pressure bonding the recording medium and another recording medium with the surface on which the image portion and the pressure phase transition layer are formed being a pressure bonding surface; having The amount of the pressure-induced phase transition particles applied to the image area is greater than the amount of the pressure-induced phase transition particles applied to the non-image area. <1> ~ <9> 13. A method for producing a printed matter according to any one of claims 1 to 12. Effect of the Invention

[0007] <1> According to the invention, in a printed matter in which a recording medium is folded and pressed onto the surface on which an image area and a pressure phase transition layer are formed, as the pressing surface, or in which a recording medium and another recording medium are stacked and pressed onto each other, as the pressing surface, a printed matter is provided in which the variation in the pressing force of the pressing surface is reduced compared to when the average thickness of the pressure phase transition layer formed on the image area and the average thickness of the pressure phase transition layer formed on the non-image area are the same on the pressing surface of the recording medium.

[0008] <2> According to the invention, a printed matter is provided in which the variation in the pressure-bonding force of the pressure-bonding surface is reduced compared to a case in which the thickness of the pressure-induced phase transition layer formed on the image area is not changed according to the thickness of the image area. <3> According to the present invention, a printed matter is provided in which the variation in the pressure-bonding force of the pressure-bonding surface is reduced, as compared with a case in which formulas (1) to (3) are not satisfied.

[0009] <4> According to the present invention, a printed matter is provided in which the variation in pressure-bonding force of the pressure-bonding surface is reduced, compared to when the coverage rate of the pressure-induced phase transition layer formed on the image area is less than 60%. <5> According to the present invention, a printed matter is provided in which the variation in the pressure-bonding force of the pressure-bonding surface is reduced compared to when the coverage rate of the pressure-induced phase transition layer formed on the non-image area is less than 10% or more than 60%.

[0010] <6> According to the invention, in a printed matter in which a recording medium is folded and pressed onto the surface on which an image portion and a pressure phase transition layer are formed, as the pressing surface, or in which a recording medium and another recording medium are stacked and pressed onto each other, as the pressing surface, a printed matter is provided in which the variation in the pressing force of the pressing surface is reduced even when the image portion is a toner image portion, compared to a case in which the average thickness of the pressure phase transition layer formed on the image portion and the average thickness of the pressure phase transition layer formed in the non-image portion are the same on the pressing surface of the recording medium.

[0011] <7> According to the invention, the pressure-induced phase transition layer contains a styrene-based resin containing styrene and other vinyl monomers as polymerization components, and a (meth)acrylic acid ester-based resin containing at least two types of (meth)acrylic acid esters as polymerization components, with the mass proportion of (meth)acrylic acid esters in the total polymerization components being less than 90 mass%, or has at least two glass transition temperatures, and a printed matter with a higher compression strength is provided than when the difference between the lowest glass transition temperature and the highest glass transition temperature among the glass transition temperatures exhibited by the pressure-induced phase transition particles is less than 30°C.

[0012] <8> According to the present invention, a printed item having a higher compression bonding strength is provided, compared to a case where the mass ratio of styrene in the total polymerization components of the styrene-based resin is less than 60 mass % or more than 95 mass %. <9> According to the present invention, a printed matter having a higher compression strength is provided compared to a case in which the mass ratio of the two (meth)acrylic esters having the largest mass proportions among at least two types of (meth)acrylic esters contained as polymerization components in the (meth)acrylic ester-based resin is less than 80:20 or exceeds 20:80.

[0013] <10> According to the invention, in a method for manufacturing a printed matter in which a recording medium is folded and pressed onto the surface on which an image area and a pressure phase transition layer are formed, which serves as a pressing surface, or in which a recording medium and another recording medium are stacked and pressed onto each other, which serves as a pressing surface on the surface on which an image area and a pressure phase transition layer are formed, a method for manufacturing a printed matter is provided in which the variation in the pressing force of the pressing surface is reduced compared to when the average thickness of the pressure phase transition layer formed on the image area and the average thickness of the pressure phase transition layer formed on the non-image area are the same on the pressing surface of the recording medium. [Brief description of the drawings]

[0014] [Figure 1] 1 is a schematic partial cross-sectional view showing an example of a recording medium before being pressed to produce a printed matter according to an embodiment of the present invention. [Diagram 2] 1 is a schematic diagram illustrating an example of a printed matter production system according to an embodiment of the present invention. [Diagram 3] FIG. 11 is a schematic diagram illustrating another example of the printed matter production system according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, embodiments of the present invention will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the embodiments.

[0016] In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of the numerical range may be replaced with a value shown in the examples.

[0017] In this specification, the term "process" includes not only an independent process but also a process that is not clearly distinguished from other processes, as long as the intended purpose of the process is achieved.

[0018] When an embodiment is described in this specification with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. Furthermore, the size of the members in each drawing is conceptual, and the relative relationship between the sizes of the members is not limited to this.

[0019] In the present specification, each component may contain multiple types of the corresponding substance. When the amount of each component in the composition is mentioned in the present specification, if multiple substances corresponding to each component are present in the composition, the total amount of the multiple substances present in the composition is meant unless otherwise specified.

[0020] In the present specification, the particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified.

[0021] In this specification, the term "(meth)acrylic" means either "acrylic" or "methacrylic".

[0022] In this specification, the term "peel strength" is an index showing the degree of peeling between the opposing surfaces (i.e., the pressure-bonded surfaces) of the recording medium, and is essentially synonymous with the "pressure-bonding property" showing the degree of pressure-bonding. In the following, when simply referring to "peel strength", it refers to the peel strength between the opposing surfaces (i.e., the pressure-bonded surfaces) of the recording medium, and when simply referring to "pressure-bonding property", it refers to the pressure-bonding property between the opposing surfaces (i.e., the pressure-bonded surfaces) of the recording medium.

[0023] [Printed material] In the printed matter of this embodiment, the recording medium is folded and pressed onto the surface on which the image area and the pressure phase transition layer are formed, or the recording medium is stacked on top of another recording medium and pressed onto the surface on which the image area and the pressure phase transition layer are formed, and the average thickness of the pressure phase transition layer formed on the image area on the pressing surface of the recording medium is greater than the average thickness of the pressure phase transition layer formed on the non-image area. Here, the "different recording medium" refers to a recording medium having a surface on which the image area and the pressure phase transition layer are formed as a pressure-bonding surface. A printed matter in which a recording medium is folded and pressed, and a printed matter in which a recording medium and another recording medium are placed on top of each other and pressed, are also called a "press-bonded printed matter".

[0024] The printed matter according to the present embodiment has the above-described configuration, and the variation in the pressure-bonding force of the pressure-bonding surface is reduced. The reason for this is presumed to be as follows.

[0025] Printed materials are known in which a recording medium is folded and pressed onto the surface that has been coated with UV varnish or water-based varnish, or in which a recording medium is placed on top of another recording medium and pressed onto the surface that has been coated with UV varnish or water-based varnish, and the two are pressed together. Also known are printed materials in which a recording medium is folded and pressed onto the surface on which the image area and the pressure phase transition layer are formed, and the surface on which the image area and the pressure phase transition layer are formed is used as the pressing surface, or in which a recording medium is stacked on top of another recording medium and pressed onto the surface on which the image area and the pressure phase transition layer are formed, and the surface on which the image area and the pressure phase transition layer are formed is used as the pressing surface.

[0026] However, in these printed materials, the pressure applied to the pressure-bonded surface varies, and localized tears or peeling may occur. This is believed to be due to a reduction in the pressure applied to the image area of ​​the pressure-bonded surface.

[0027] Therefore, in the printed matter according to the present embodiment, the average thickness of the pressure-induced phase transition layer formed on the image area on the pressure-bonding surface of the recording medium is made larger than the average thickness of the pressure-induced phase transition layer formed on the non-image area, thereby suppressing the reduction in the pressure-bonding force on the image area of ​​the pressure-bonding surface, thereby suppressing the occurrence of variations in the pressure-bonding force on the pressure-bonding surface.

[0028] From the above, it is presumed that the printed matter according to this embodiment has the above-mentioned configuration, and thus reduces the variation in the pressure-bonding force of the pressure-bonding surface. Here, printed matter that is laminated by folding in thirds, such as in a Z fold, and printed matter that is folded in half, such as in a V fold, have the advantage of being able to store more information, but because there are four laminated surfaces, variations in the bonding force of the laminated surfaces have a significant effect, and they are particularly prone to localized tearing or peeling. However, even when the printed matter according to this embodiment is folded in three, such as in a Z-fold, and pressed, the variation in the pressing force of the pressed surface is reduced, thereby suppressing localized tearing or peeling.

[0029] The printed matter according to this embodiment will be described in detail below.

[0030] (Image area, pressure phase transition layer and recording medium) The image portion may be a toner image portion formed on the recording medium using an electrophotographic method, an ink image portion formed using an inkjet method, etc. In particular, when a toner image portion is present, the pressing force is reduced and the pressing force of the pressing surface is likely to vary, but in this embodiment, the variation in the pressing force of the pressing surface is suppressed. The pressure-induced phase transition layer may be a layer in which pressure-induced phase transition particles are applied and fixed on a recording medium. Examples of recording media include paper, coated paper in which the surface of paper is coated with resin or the like, cloth, nonwoven fabric, resin film, and resin sheet. The image area and the pressure phase transition layer will be described in detail in the method for producing a printed matter described below.

[0031] (Thickness of pressure phase transition layer) In the printed matter according to this embodiment, the average thickness of the pressure-induced phase transition layer formed on the image area on the pressure-bonded surface of the recording medium is greater than the average thickness of the pressure-induced phase transition layer formed on the non-image area (see FIG. 1). In FIG. 1, G10 indicates the image area, PL10 indicates the pressure phase change layer formed on the non-image area, PL12 indicates the pressure phase change layer formed on the image area, T10 indicates the thickness of the pressure phase change layer formed on the non-image area, and T12 indicates the thickness of the pressure phase change layer formed on the image area. FIG. 1 shows a schematic partial cross-sectional view illustrating an example of a recording medium before being pressed to produce a printed matter by Z-folding.

[0032] Specifically, from the viewpoint of suppressing variation in the pressure-bonding force of the pressure-bonding surface, it is preferable that the thickness of the pressure-induced phase transition layer formed on the image area is thicker as the image area becomes thicker, because the pressure-bonding force tends to decrease as the image area becomes thicker. More specifically, when the average thickness of the pressure phase transition layer formed on the image area is 0.5 μm or more and 5.0 μm or less, the average thickness of the image area is more than 0 μm and 5.0 μm or less, and the thickness BR of the image area is 0.5 μm or less, it is preferable that the following formulas (1) to (3) are satisfied. Formula (1): AR=X1×BR+Y1 (Formula 1) Formula (2): 2≦X1≦10 Formula (3): 0.5≦Y1≦2 (In formula (1), AR indicates the thickness (μm) of the pressure-induced phase transition layer formed on the image area, and BR indicates the thickness (μm) of the image area. However, the thicknesses indicated by AR and BR are the thickness of the pressure-induced phase transition layer directly above the image area and the thickness of the image area directly below the pressure-induced phase transition layer for which the thickness was calculated.)

[0033] When the thickness of the pressure phase transition layer formed on the image area and the average thickness of the image area are within the above ranges, and the thickness BR of the image area is 0.5 μm or less, satisfying formulas (1) to (3) suppresses a decrease in the pressure bonding force in the image area. However, when the thickness of the image portion exceeds 0.5 μm, the increase in pressure bonding force reaches saturation, so it is advisable not to change the thickness of the pressure-induced phase transition layer.

[0034] Here, from the viewpoint of suppressing variation in the pressure-bonding force of the pressure-bonding surface, the value of X1 in formula (2) is preferably 2.5 or more and 7 or less, and more preferably 3 or more and 5 or less. From the same viewpoint, the Y1 value in formula (3) is preferably 0.7 or more and 1.4 or less, and more preferably 0.8 or more and 1.3 or less.

[0035] The thickness of the pressure phase transition layer and the thickness of the image area are measured as follows. The pressure is released and the printed matter is unfolded (i.e., the pressure-bonded surfaces of the printed matter are peeled away from each other), and a sample is taken from the unfolded matter with its cross section as the observation surface. A sample is cut so that an image portion and a non-image portion, which are to be used for cross-sectional observation, are located at the ends, and the cross-section is observed using a laser microscope. Then, the thickness of the pressure-induced phase transition layer is measured at five locations, and the average value is regarded as the "thickness of the pressure-induced phase transition layer formed on the non-image area." The thickness of the image area is measured at five locations, and the average value is regarded as the "average thickness of the image area." In addition, whether or not formula (1) is satisfied is determined by measuring the thickness of the image area and the pressure-induced phase transition layer formed on the image area at three locations where the image area has a different thickness, and plotting and graphing the thickness of the pressure-induced phase transition layer on the vertical axis and the thickness of the image area on the horizontal axis.

[0036] (Coverage of pressure phase transition layer) The coverage of the pressure phase transition layer formed on the image area is preferably 60% or more and 100% or less, more preferably, and even more preferably. By setting the coverage rate of the pressure-induced phase transition layer formed on the image area within the above range, the pressure-induced phase transition layer can sufficiently cover the paper surface, which makes it easier to suppress variations in the pressure-bonding force of the pressure-bonding surface.

[0037] The coverage of the pressure phase transition layer formed in the non-image area is preferably from 10% to 60%, more preferably from 15% to 55%, and even more preferably from 20% to 50%. By setting the coverage rate of the pressure-induced phase transition layer formed on the non-image area within the above range, the pressure-induced phase transition layer can adequately cover the paper surface, which makes it easier to suppress variations in the pressure-bonding force of the pressure-bonding surface.

[0038] The coverage of the pressure phase change layer is measured as follows. A sample is taken from the area where the pressure phase transition layer is formed, and an observation image is obtained at 1000 times magnification using a SEM microscope or the like. The pressure transition layer is extracted by binarizing the obtained image, and its proportion of the whole is measured. This is done at three points, and the average is taken as the coverage rate.

[0039] (Form of printed matter) Examples of printed matter in this embodiment include printed matter in which a recording medium is folded and laminated, with the surface on which the image portion and the pressure phase transition layer are formed serving as the bonding surface (printed matter laminated in three folds such as a Z fold, and printed matter laminated in two folds such as a V fold), and printed matter in which a recording medium and another recording medium are laminated and laminated, with the surface on which the image portion and the pressure phase transition layer are formed serving as the bonding surface. A representative example of the printed matter according to this embodiment is a pressure-bonded postcard.

[0040] [Printed matter manufacturing method and printed matter manufacturing system] The method for producing a printed matter according to the present embodiment includes the steps of: a pressure-induced phase transition particle applying step of applying pressure-induced phase transition particles onto the recording medium on which the image area is formed; a fixing step of fixing at least the pressure-induced phase transition particles onto a recording medium to form a pressure-induced phase transition layer; a pressure bonding step of folding and pressing the recording medium with the surface on which the image area and the pressure phase transition layer are formed as a pressure bonding surface, or of stacking and pressing the recording medium and another recording medium with the surface on which the image area and the pressure phase transition layer are formed as a pressure bonding surface; has. In the method for producing a printed matter according to this embodiment, the amount of pressure-induced phase transition particles applied to the image area is greater than the amount of pressure-induced phase transition particles applied to the non-image area in order to produce a printed matter according to the above embodiment.

[0041] The method for producing a printed matter according to this embodiment is carried out by a system for producing a printed matter according to this embodiment, which will be described below. The printing production system according to the present embodiment includes: a pressure-induced phase transition particle applying section that contains pressure-induced phase transition particles and applies the pressure-induced phase transition particles onto a recording medium on which an image area is formed; a fixing section for fixing at least the pressure-induced phase transition particles onto a recording medium to form a pressure-induced phase transition layer; a pressure bonding section for folding and bonding the recording medium with the surface on which the image area and the pressure phase transition layer are formed as a bonding surface, or for bonding the recording medium and another recording medium with the surface on which the image area and the pressure phase transition layer are formed as a bonding surface; Equipped with.

[0042] The image portion is a region in which a chromatic image is formed, and is not particularly limited as long as the image contains a coloring material. For example, the image portion may be an image having an average light transmittance of less than 90% in the visible region (400 nm or more and 700 nm or less). The average light transmittance in the chromatic image is preferably less than 50%, more preferably less than 50%, and even more preferably less than 10%. The average transmittance is measured using a spectrophotometer V700 (manufactured by JASCO Corporation).

[0043] The terms "pressure phase change layer" and "pressure phase change particles" refer to a layer and particles that undergo a phase change due to pressure, and specifically refer to a layer and particles that satisfy the following formula 1. Formula 1...10℃≦T1-T2 In formula 1, T1 is the temperature at which the viscosity is 10,000 Pa s under a pressure of 1 MPa, and T2 is the temperature at which the viscosity is 10,000 Pa s under a pressure of 10 MPa. How to determine temperatures T1 and T2 will be described later.

[0044] The "pressure phase transition layer" and "pressure phase transition particles" have at least two glass transition temperatures, including a styrene-based resin containing styrene and other vinyl monomers as polymerization components, and a (meth)acrylic acid ester-based resin containing at least two (meth)acrylic acid esters as polymerization components, with the mass ratio of the (meth)acrylic acid esters to the total polymerization components being 90 mass % or more, and it is preferable that the difference between the lowest glass transition temperature and the highest glass transition temperature of the "pressure phase transition layer" and "pressure phase transition particles" is 30° C. or more. The reason is as follows.

[0045] Generally, styrene resins and (meth)acrylic acid ester resins have low compatibility with each other, so it is believed that the two resins are contained in the particles in a phase-separated state. In addition, when the layer and particles are pressurized, the (meth)acrylic acid ester resin, which has a relatively low glass transition temperature, is first fluidized, and this fluidization spreads to the styrene resin, so that both resins are fluidized. In addition, it is believed that the two resins in the layer and particles, when solidified by reducing pressure after being fluidized by pressurization, form a phase-separated state again due to their low compatibility. It is presumed that a (meth)acrylic acid ester-based resin containing at least two kinds of (meth)acrylic acid esters as polymerization components has at least two kinds of ester groups bonded to the main chain, and therefore has a lower degree of molecular alignment in the solid state compared to a (meth)acrylic acid ester homopolymer, and therefore is more likely to be fluidized by pressure. Furthermore, when the mass ratio of (meth)acrylic acid esters to the entire polymerization components is 90 mass% or more, at least two kinds of ester groups are present at high density, and therefore the degree of molecular alignment in the solid state is lower, and therefore it is presumed that the resin is more likely to be fluidized by pressure. Therefore, it is presumed that the "pressure phase change layer" and "pressure phase change particles" configured as described above are easily fluidized by pressure, that is, are easily subjected to a phase transition by pressure. In addition, a (meth)acrylic acid ester-based resin containing at least two types of (meth)acrylic acid esters in the polymerization components, with the mass ratio of the (meth)acrylic acid esters in the total polymerization components being 90 mass% or more, has a low degree of molecular alignment even when solidified again, and is therefore presumed to result in a minute phase separation with the styrene-based resin. It is presumed that the finer the state of phase separation between the styrene-based resin and the (meth)acrylic acid ester-based resin, the more uniform the state of the fixing surface with respect to the fixing target object becomes, and the better the pressure-bonding ability by pressure-bonding. Therefore, it is presumed that the "pressure-induced phase transition layer" and the "pressure-induced phase transition particles" have excellent compression bonding properties.

[0046] Hereinafter, each step of the method for producing a printed matter according to this embodiment will be described together with each unit of the system for producing a printed matter according to this embodiment.

[0047] <Pressure-induced phase transition particle application step and pressure-induced phase transition particle application unit> In the application step, in a pressure phase transition particle application section (hereinafter also referred to as "application section"), pressure phase transition particles are applied onto the recording medium on which an image area has been formed. There are no particular limitations on the pressure-induced phase transition particle application means in the application section, and any means can be used as long as it can apply pressure-induced phase transition particles to the surface of the recording medium in the desired amount and at the desired application position. Specific examples of pressure-induced phase transition particle application methods include a spraying method in which pressure-induced phase transition particles are sprayed, a coating method in which pressure-induced phase transition particles are applied, and an electrophotographic method in which pressure-induced phase transition particles are used as toner.

[0048] (Position where pressure phase transition particles are applied) The pressure-induced phase transition particles may be applied to the entire surface of the recording medium or to a part of the surface. The pressure phase transition particles are applied to the image area and non-image area of ​​the pressure-bonded surface of the recording medium.

[0049] Here, the pressure-induced phase transition particles are preferably transparent, as described below. By using pressure-induced phase transition particles that are transparent, even when the pressure-induced phase transition particles are applied onto an image area of ​​a recording medium to form a pressure-induced phase transition layer, the visibility of the image area is ensured. In addition, "transparent" means that the average transmittance of light in the visible range (400 nm or more and 700 nm or less) in the area to which the pressure-induced phase transition particles are applied is 10% or more, preferably 50% or more, more preferably 80% or more, and even more preferably 90% or more. The average transmittance is measured using a spectrophotometer V700 (manufactured by JASCO Corporation).

[0050] (Pressure phase transition particle application state) The pressure-induced phase transition particles may be applied in a state in which the particle shape is retained, or in a state in which the pressure-induced phase transition particles are aggregated to form a layer, and from the viewpoint of obtaining sufficient peel strength (or pressure bonding property by pressure bonding), a layered state is preferable. The layer of pressure phase change particles may be a continuous layer or a discontinuous layer.

[0051] The amount of pressure-induced phase transition particles applied is set to 0.5 g / m from the viewpoint of obtaining sufficient compression bonding. 2 More than 8.0g / m 2 It is preferable that the content is 0.8 g / m or less. 2 More than 6.0g / m 2 More preferably, it is 1.0 g / m or less. 2 More than 4.5g / m 2 It is even more preferable that: However, the amount of pressure-induced phase transition particles applied to the image area is set to be greater than the amount of pressure-induced phase transition particles applied to the non-image area.

[0052] (Addition of pressure phase transition particles) As described above, the application of pressure-induced phase transition particles is not particularly limited as long as the pressure-induced phase transition particles are applied to the desired application position, and specifically, a spraying method in which pressure-induced phase transition particles are sprayed, a coating method in which pressure-induced phase transition particles are applied, an electrophotographic method in which pressure-induced phase transition particles are used as toner, etc. are used. The pressure-induced phase transition particles may be applied by directly dropping the particles onto the recording medium or by roll coating. As long as the pressure-induced phase transition particles are applied to the recording medium, the application method of the pressure-induced phase transition particles is not particularly limited. Examples of application sections that apply pressure-induced phase transition particles onto a recording medium include, as described above, application sections that use a spraying method in which pressure-induced phase transition particles are sprayed, application sections that use a coating method in which pressure-induced phase transition particles are applied, and application sections that use an electrophotographic method in which pressure-induced phase transition particles are used as toner.

[0053] The application process by the spraying method includes, for example, a step of preparing a dispersion liquid in which pressure phase transition particles are dispersed, a step of spraying the dispersion liquid onto a recording medium, and a step of drying the dispersion liquid sprayed onto the recording medium. The spray application unit includes, for example, a spraying unit that sprays a dispersion liquid in which pressure phase transition particles are dispersed onto the recording medium, and a drying unit that dries the dispersion liquid sprayed onto the recording medium. The blowing means may be, for example, a spray, etc. The drying means may be, for example, a hot air blower, a near-infrared heater, a laser irradiation device, etc.

[0054] The application step by the coating method may, for example, include a step of applying pressure-induced phase transition particles to a recording medium. In the coating method, a coating liquid in which pressure-induced phase transition particles are dispersed may be used. The application step by the coating method using a coating liquid may, for example, include a step of preparing a coating liquid in which pressure-induced phase transition particles are dispersed, a step of applying the coating liquid to a recording medium, and a step of drying the coating liquid applied to the recording medium. The application unit using a coating method may include, for example, a coating unit that applies pressure phase transition particles to a recording medium. The application unit using a coating method that uses a coating liquid may include, for example, a coating unit that applies the coating liquid to the recording medium, and a drying unit that dries the coating liquid applied to the recording medium. The coating means may be, for example, a roll.

[0055] The application process using the electrophotographic method includes, for example, a charging process of charging the surface of an image carrier, an electrostatic image forming process of forming an electrostatic image on the charged surface of the image carrier, a developing process of developing the electrostatic image formed on the surface of the image carrier as a pressure phase transition particle region using an electrostatic image developer containing pressure phase transition particles, and a transfer process of transferring the pressure phase transition particle region formed on the surface of the image carrier to the surface of a recording medium. The electrophotographic application unit includes, for example, an image carrier, a charging means for charging the surface of the image carrier, an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier, a developing means for containing an electrostatic image developer containing pressure phase transition particles and developing the electrostatic image formed on the surface of the image carrier as a pressure phase transition particle area by the electrostatic image developer, and a transfer means for transferring the pressure phase transition particle area formed on the surface of the image carrier to the surface of a recording medium.

[0056] The electrophotographic application section may have a cartridge structure (so-called process cartridge) in which a section including a developing means is detachably attached to a particle application device. As the process cartridge, for example, a process cartridge that includes a developing means that contains an electrostatic image developer including pressure phase transition particles and is detachably attached to a particle application device is preferably used. The electrophotographic application method and application unit may both use an electrophotographic image forming method and image forming apparatus, and may use known processes and means employed in the electrophotographic image forming method and image forming apparatus. The electrophotographic application method and application unit may employ an intermediate transfer method, in which, for example, a pressure phase transition particle region formed on the surface of an image carrier is first transferred to the surface of an intermediate transfer body, and then finally transferred from the surface of the intermediate transfer body to the surface of a recording medium. Furthermore, the electrophotographic application method and application unit may include means and steps other than those described above, such as a step and means for cleaning the surface of the image carrier, or an apparatus equipped with a discharging means for irradiating the surface of the image carrier with discharging light to dissipate electricity.

[0057] When using a recording medium on which an image area has been formed, the pressure-induced phase transition particles may be applied to the recording medium on which an image area has already been formed, or the image formation process for forming an image area on the recording medium and the application process may be carried out consecutively. Examples of the method of continuously performing the image forming step and the application step include a method of performing the application step after the image forming step using an inkjet recording method, a method of performing both the image forming step and the application step by an electrophotographic method, etc. Specifically, for example, there is a method of forming a composite image portion on the surface of a recording medium using both a color material for image formation (preferably a colored ink) in the image forming step and pressure phase transition particles in the application step.

[0058] <Fixing process and fixing section> In the fixing step, at least the pressure-induced phase transition particles are fixed onto the recording medium to form a pressure-induced phase transition layer. Specifically, in the fixing step, for example, the pressure phase transition particles applied to the recording medium are heated in a fixing section. When an unfixed toner image portion is formed on the recording medium as the image portion, the fixing step may be a step of fixing the unfixed toner image portion together with the pressure phase transition particles.

[0059] There are no particular limitations on the means for heating the pressure-induced phase transition particles (hereinafter also referred to as "particle heating means"), and any means capable of heating the pressure-induced phase transition particles applied onto the recording medium formed on the recording medium may be used. The means for heating the pressure-induced phase transition particles (particle heating means) may be of a contact type or a non-contact type. Examples of the contact type particle heating means include a method in which a member such as a roll, belt, or pad is heated and the heated member is brought into contact with the pressure-induced phase transition particles. Examples of non-contact particle heating means include a method in which a recording medium on which a chromatic image has been formed and on which pressure-induced phase transition particles have been applied is passed through an area heated by a heater, oven, etc., and a method in which the pressure-induced phase transition particles are heated by irradiation light from a halogen lamp, xenon lamp, etc.

[0060] Among these, the fixing step preferably uses a contact type particle heating means from the viewpoint of being able to heat the pressure-induced phase transition particles and to prevent the pressure-induced phase transition particles from moving or falling off. That is, the particle heating means is preferably a contact type particle heating means.

[0061] (Heating of Pressure Phase Change Particles in Contact Mode) When heating pressure-induced phase-transition particles by the contact method, the set temperature of the member (also called the contact member) that comes into contact with the pressure-induced phase-transition particles may be any temperature that can plasticize the pressure-induced phase-transition particles, but from the viewpoint of the heating efficiency of the pressure-induced phase-transition particles, the set temperature is preferably, for example, 120°C or higher and 250°C or lower, more preferably 130°C or higher and 200°C or lower, and even more preferably 150°C or higher and 180°C or lower. Here, the set temperature of the contact member refers to a target value of the surface temperature of the contact member that comes into contact with the pressure phase transition particles. The contact member is not particularly limited as long as it has a surface heated to the above-mentioned set temperature, and examples thereof include a roll, a belt, a pad, and the like.

[0062] The fixing step is preferably a step in which the pressure phase transition particles are heated and pressurized. By heating and pressurizing the pressure-induced phase change particles, smoothness can be imparted to the surface to which the pressure-induced phase change particles are applied (for example, the surface of the pressure-induced phase change particle layer). The pressure applied to the pressure phase transition particles in the fixing step may be, for example, a pressure applied by a fixing means in an electrophotographic system.

[0063] Examples of the means for heating and pressurizing the pressure-induced phase transition particles (also called a heating and pressurizing member) include the following. That is, examples of such a device include a heating and pressurizing roll pair which is a pair of two contacting rolls, at least one of which applies heat, and a recording medium on which a chromatic image has been formed and to which pressure-induced phase transition particles have been applied is passed between the pair of rolls to apply heat and pressure; a heating and pressurizing member which is a member in contact with a roll and a belt, at least one of which applies heat, and a recording medium on which a chromatic image has been formed and to which pressure-induced phase transition particles have been applied is passed between these members to apply heat and pressure; and a heating and pressurizing belt pair which is a pair of two contacting belts, at least one of which applies heat, and a recording medium on which a chromatic image has been formed and to which pressure-induced phase transition particles have been applied is passed between the pair of belts to apply heat and pressure.

[0064] <Crimping process and crimping section> In the pressure bonding step, the recording medium is folded and pressure bonded with the surface on which the image area and the pressure phase transition layer are formed serving as the pressure bonding surface, or the recording medium is superimposed on another recording medium and pressure bonded with the surface on which the image area and the pressure phase transition layer are formed serving as the pressure bonding surface. Hereinafter, the recording medium on which the image area and the pressure phase transition layer are formed is also referred to as the "recording medium after application".

[0065] Specifically, in the pressing process, a laminate formed by folding a recording medium on which an image portion and a pressure phase transition particle layer are formed (i.e., the recording medium after application) with a pressure phase transition layer interposed therebetween, or a laminate formed by stacking the recording medium after application on which an image portion and a pressure phase transition layer are formed and another recording medium with a pressure phase transition layer interposed therebetween, is pressed in the thickness direction. The folded form of the recording medium after application may be, for example, folded in two, folded in three, folded in four, or may be folded in only a part of the recording medium. At this time, the pressure phase transition layer fixed in the fixing step is disposed on two opposing surfaces of the recording medium after application. The form of overlapping between the applied recording medium and another recording medium may be, for example, a form in which another recording medium is overlapped on the applied recording medium, or a form in which another recording medium is overlapped at each of a plurality of locations on the applied recording medium. Here, the other recording medium may be a recording medium on which an image is formed in advance on one or both sides, a recording medium on which no image portion is formed, or a pressure-bonded printed matter that has been prepared in advance. At this time, the pressure-phase transition particles fixed in the fixing process are arranged on the two opposing surfaces of the applied recording medium and the other recording medium.

[0066] The means for pressurizing the laminate (laminate pressurizing means) is not particularly limited as long as it is a means capable of pressurizing the laminate in the thickness direction, and may be a means for passing the laminate between a pair of spaced rolls, or a means for pressing the laminate using a press or the like.

[0067] Among these, the pressure bonding step is preferably a step of inserting the laminate between a pair of rolls spaced apart by a distance C and pressing the laminate in the thickness direction. That is, the laminate pressing means is preferably a means for inserting the laminate between a pair of rolls spaced apart by a distance C, and pressing the laminate in the thickness direction. Here, the distance C may be appropriately determined based on the thickness of the laminate to be pressed, from the viewpoint of obtaining the desired peel strength (or compression bonding property), and is, for example, preferably 0.01 mm or more and 0.40 mm or less, more preferably 0.05 mm or more and 0.30 mm or less, and even more preferably 0.10 mm or more and 0.25 mm or less.

[0068] (Pressurization conditions) The maximum pressure applied in the thickness direction of the laminate (hereinafter also referred to as "bonding pressure") is preferably 48 MPa or more and 120 MPa or less, more preferably 60 MPa or more and 110 MPa or less, and even more preferably 80 MPa or more and 100 MPa or less. A bonding pressure of 48 MPa or more makes it easy to obtain sufficient bonding properties through bonding, while a bonding pressure of 120 MPa or less makes it easy to prevent the recording medium from being torn or deformed when pressure is applied. The bonding pressure is measured using a commercially available pressure measuring film. A specific example of the pressure measuring film is the pressure measuring film Prescale manufactured by Fujifilm Corporation. The maximum pressure refers to the maximum value of the change in pressure while pressure is applied to the laminate by the laminate pressurizing means.

[0069] The laminate pressing means may be a commercially available device, specific examples of which include PRESSLE LEADA, PRESSLE CORE, and PRESSLE Bee manufactured by Toppan Forms Co., Ltd., and PS-500H, PS-500, EX-4100WI, EX-4100W, EX-4100 / 4150, and PS-100 manufactured by Duplo Seiko Co., Ltd.

[0070] The compression step may be performed without heating or with heating. In other words, the laminate pressurizing means may not include a heating means and may pressurize the laminate without heating, or may include a heating means and may pressurize the laminate while heating it.

[0071] The method for producing a printed matter according to this embodiment may include other steps in addition to the application step, the fixing step, and the pressure bonding step. Other steps include a step of forming an image area on the recording medium before applying pressure-induced phase transition particles, and a step of cutting the recording medium after the application step and the laminate after the pressure-bonding step to the desired size.

[0072] <Example of manufacturing system and manufacturing method> An example of a printed matter production system according to the present embodiment will be shown below, and a printed matter production method according to the present embodiment will be described, but the present embodiment is not limited to this.

[0073] Fig. 2 is a schematic diagram showing an example of a system for producing printed matter according to the present embodiment. The system for producing printed matter shown in Fig. 2 includes a printing means 500 that simultaneously performs the formation of an image portion on a recording medium by an inkjet method and the application of pressure phase transition particles, and a pressure bonding means 200 disposed downstream of the printing means 500. The arrow indicates the transport direction of the recording medium.

[0074] The printing means 500 includes an inkjet recording head 520, which serves as an example of an image forming section, for ejecting ink droplets onto the recording medium P to form an image portion. A particle application device 518 is disposed downstream in the transport direction of the recording medium P (the direction of the arrow in the figure) from the inkjet recording head 520, as an example of an application section that applies pressure phase transition particles 516 to the surface of the recording medium P. This application device 518 is an example of an application section that applies pressure phase transition particles to the recording medium by a coating method.

[0075] The printing means 500 also includes a recording medium storage section (not shown) that stores the recording medium P, a transport section (not shown) that transports the recording medium P stored in the recording medium storage section, a fixing device 564 that fixes the ink droplets and pressure phase transition particles 516 applied to the recording medium P to the recording medium P, and a recording medium discharge section (not shown) from which the recording medium P to which the ink droplets and pressure phase transition particles 516 have been fixed by the fixing device 564 is discharged.

[0076] The fixing device 564 includes a heating roll 564A incorporating a heat source, and a pressure roll 564B disposed opposite to the heating roll 564A.

[0077] The particle applying device 518 is a device that supplies pressure phase transition particles 516 to the surface of the recording medium P, and forms a pressure phase transition particle region 516A on the surface of the recording medium P. The particle applying device 518 is provided with a supply roll 518A in a portion facing the recording medium P, and applies pressure phase transition particles 516 to a corresponding application region. In the particle application device 518, pressure phase transition particles 516 are supplied to a supply roll 518A (conductive roll), and the amount of pressure phase transition particles 516 applied onto the recording medium P (i.e., the layer thickness of the pressure phase transition particle region 516A applied in layer form onto the recording medium P) is adjusted.

[0078] The inkjet recording head 520 includes an inkjet recording head 520Y that ejects yellow ink droplets from its nozzles, an inkjet recording head 520M that ejects magenta ink droplets from its nozzles, an inkjet recording head 520C that ejects cyan ink droplets from its nozzles, and an inkjet recording head 520K that ejects black ink droplets from its nozzles. These inkjet recording heads 520 are driven by a piezoelectric type, a thermal type, or the like. The inkjet recording head 520 may be a recording head that has a recording width equal to or larger than the area to be recorded and that ejects droplets onto the recording medium P to record an image without moving in a direction intersecting the transport direction of the recording medium P, or may be a recording head that ejects droplets onto the recording medium P while moving in a direction intersecting the transport direction of the recording medium P to record an image. In addition, the ink ejected by the inkjet recording head 520 can be either water-based or oil-based, but water-based ink is more suitable for use in terms of environmental friendliness. Water-based ink contains an ink solvent (e.g., water, water-soluble organic solvent) in addition to a recording material such as a coloring material. In addition, it may contain other additives as necessary.

[0079] In the printing means 500, first, the recording medium P is transported by a transport unit from a recording medium storage unit to the position of the inkjet recording head 520, and ink droplets of each color are applied by the inkjet recording head 520 to form an image area on the recording medium P. Next, when the recording medium P on which the image area has been formed is transported by the transport unit to the position of a particle application device 518, pressure phase transition particles 516 are applied by the particle application device 518 onto the recording medium P to form a pressure phase transition particle region 516A. The recording medium P on which the image area and the pressure phase transition particle region 516A are formed is then transported to a fixing device 564 (an example of a fixing section). The pressure applied to the recording medium P by the fixing device 564 may be lower than the pressure applied to the recording medium P by the pressure device 230, and specifically, is preferably 0.2 MPa or more and 1 MPa or less. The surface temperature of the recording medium P when heated by the heating roll 564A of the fixing device 564 is preferably 150°C or more and 220°C or less, more preferably 155°C or more and 210°C or less, and even more preferably 160°C or more and 200°C or less.

[0080] In the manner described above, the recording medium P passes through the printing means 500, and becomes a post-application recording medium P1 on which an image portion is formed and pressure-induced phase transition particles are applied. Next, after application of the toner, the recording medium P1 is transported towards the pressing means 200.

[0081] In the printing system according to this embodiment, the printing means 500 and the pressing means 200 may be disposed close to each other or separated from each other. When the printing means 500 and the pressing means 200 are separated from each other, the printing means 500 and the pressing means 200 are connected by, for example, a conveying means (for example, a belt conveyer) that conveys the recording medium P1 after application of the toner.

[0082] The pressing means 200 includes a folding device 220 and a pressure device 230, and is a means for folding and pressing the recording medium P1 after application of the recording medium P1.

[0083] The folding device 220 folds the applied recording medium P1 passing through the device, and creates a folded recording medium, that is, a laminate P2. In addition, in the folded recording medium (that is, the laminate), pressure phase transition particles applied by the printing means 500 are disposed on at least a portion of at least one of the two opposing surfaces of the recording medium.

[0084] The pressing means 200 may be provided with a stacking device, instead of the folding device 220, which stacks the recording medium and another recording medium after the application of the pressure-applied mark. The recording medium obtained by the overlapping device, i.e., the laminate, has pressure-induced phase transition particles applied by the printing means 500 arranged on at least a portion of at least one of the two opposing surfaces of the recording medium and another recording medium after application.

[0085] The laminate P2 that has left the folding device 220 (or the overlapping device) is transported toward the pressing device 230.

[0086] The pressure device 230 includes, for example, a pair of pressure members (i.e., pressure rolls 231 and 232). The pressure roll 231 and the pressure roll 232 are separated by, for example, a distance C, and pressure is applied to the laminate P2 in the thickness direction by passing the laminate P2 between the pair of rolls. The pair of pressure members included in the pressure device 230 is not limited to a combination of a pressure roll and a pressure roll, and may also be a combination of a pressure roll and a pressure belt, or a combination of a pressure belt and a pressure belt.

[0087] The pressurizing device 230 may or may not have a heat source (e.g., a halogen heater) for heating the laminate P2 inside. When the pressurizing device 230 has a heat source inside, the surface temperature of the laminate P2 when heated by the heat source is preferably 30° C. or more and 120° C. or less, more preferably 40° C. or more and 100° C. or less, and even more preferably 50° C. or more and 90° C. or less. Note that the fact that the pressurizing device 230 does not have a heat source inside does not exclude the temperature inside the pressurizing device 230 becoming equal to or higher than the ambient temperature due to heat generated by a motor or the like provided in the pressurizing device 230.

[0088] When pressure is applied to the laminate P2 passing through the pressure device 230, the folded surfaces are fixed together by the fluidized pressure-induced phase transition particles, and a pressure-bonded print P3 is produced. In the produced pressure-bonded print P3, the opposing surfaces are partially or entirely fixed to each other.

[0089] The completed pressure-bonded printed matter P3 is conveyed out of the pressure device 230.

[0090] The first type of the pressure-bonded printed matter P3 is a pressure-bonded printed matter in which the recording medium is folded over and fixed on the opposing surfaces by pressure-induced phase transition particles. The laminated printed product P3 is produced by a printing product production system including a folding device 220.

[0091] The second type of the pressure-bonded print P3 is a pressure-bonded print in which a plurality of overlapping recording media are fixed on opposing surfaces by pressure-induced phase transition particles. The laminated printed product P3 is produced by a laminated printed product production system that includes a laminating device.

[0092] The printed matter manufacturing system according to this embodiment is not limited to an apparatus in a form in which the stack P2 is transported continuously from the folding device 220 (or the overlapping device) to the pressing device 230. The printed matter manufacturing system of this embodiment may be an apparatus that stores the stack P2 that leaves the folding device 220 (or stacking device), and after the stored amount of the stack P2 reaches a predetermined amount, transports the stack P2 to the pressure device 230.

[0093] In the printed matter manufacturing system according to this embodiment, the folding device 220 (or the overlapping device) and the pressure device 230 may be in close proximity to each other or may be spaced apart from each other. When the folding device 220 (or the overlapping device) and the pressure device 230 are spaced apart from each other, the folding device 220 (or the overlapping device) and the pressure device 230 are connected by, for example, a conveying means (for example, a belt conveyor) that conveys the laminate P2.

[0094] Furthermore, the printing production system according to the present embodiment may include a cutting means for cutting the recording medium to a predetermined size. The cutting means may be, for example, a cutting means arranged between the printing means 300 and the bonding means 200, which cuts off a part of the recording medium P1 after application, where the pressure-induced phase transition particles are not arranged; a cutting means arranged between the folding device 220 and the pressing device 230, which cuts off a part of the laminate P2, where the pressure-induced phase transition particles are not arranged; a cutting means arranged downstream of the bonding means 200, which cuts off a part of the bonded printed matter P3, where the pressure-induced phase transition particles are not fixed; etc. The cutting means may cut off a part of the region where the pressure-induced phase transition particles are arranged.

[0095] The printed matter manufacturing system according to the present embodiment is not limited to a sheet-fed type device. The printed matter manufacturing system according to the present embodiment may be a device that performs a placement process and a pressing process on a long recording medium to form a long-length pressed-on printed matter, and then cuts the long-length pressed-on printed matter to a predetermined size.

[0096] Fig. 3 is a schematic diagram showing an example of a system for producing printed matter according to the present embodiment. The system for producing printed matter shown in Fig. 3 includes a printing unit 300 that simultaneously forms an image area on a recording medium and applies pressure phase transition particles, and a pressure bonding unit 200 disposed downstream of the printing unit 300.

[0097] The printing means 300 is a 5-tandem type intermediate transfer type printing means. The printing means 300 includes a unit 10T that applies pressure phase transition particles (T), and units 10Y, 10M, 10C, and 10K that form images of the respective colors of yellow (Y), magenta (M), cyan (C), and black (K). The unit 10T is a particle applying means (i.e., applying section) that applies pressure phase transition particles onto the recording medium P using a developer containing pressure phase transition particles. The units 10Y, 10M, 10C, and 10K are means that form colored images (i.e., image sections) on the recording medium P using developers containing colored toners. The units 10T, 10Y, 10M, 10C, and 10K employ an electrophotographic system.

[0098] The units 10T, 10Y, 10M, 10C, and 10K are arranged in parallel and spaced apart from one another in the horizontal direction. The units 10T, 10Y, 10M, 10C, and 10K may be process cartridges that are detachably attached to the printing means 300.

[0099] An intermediate transfer belt (an example of an intermediate transfer body) 20 is provided below the units 10T, 10Y, 10M, 10C, and 10K and extends through each unit. The intermediate transfer belt 20 is provided wrapped around a drive roll 22, a support roll 23, and an opposing roll 24, which are in contact with the inner surface of the intermediate transfer belt 20, and runs in a direction from the unit 10T toward the unit 10K. An intermediate transfer body cleaning device 21 is provided on the image bearing surface side of the intermediate transfer belt 20, facing the drive roll 22.

[0100] The units 10T, 10Y, 10M, 10C, and 10K are respectively equipped with developing devices (examples of developing means) 4T, 4Y, 4M, 4C, and 4K. Pressure phase transition particles, yellow toner, magenta toner, cyan toner, and black toner contained in cartridges 8T, 8Y, 8M, 8C, and 8K are supplied to the developing devices 4T, 4Y, 4M, 4C, and 4K, respectively.

[0101] Since the units 10T, 10Y, 10M, 10C, and 10K have the same configuration and operation, the unit 10T that applies pressure phase transition particles onto a recording medium will be described as a representative.

[0102] The unit 10T has a photoconductor (an example of an image carrier) 1T. Around the photoconductor 1T, a charging roll (an example of a charging means) 2T that charges the surface of the photoconductor 1T, an exposure device (an example of an electrostatic image forming means) 3T that exposes the surface of the charged photoconductor 1T to a laser beam to form an electrostatic image, a development device (an example of a development means) 4T that supplies pressure phase transition particles to the electrostatic image to develop the electrostatic image and form a pressure phase transition particle region, a primary transfer roll (an example of a primary transfer means) 5T that transfers the pressure phase transition particle region formed by development onto the intermediate transfer belt 20, and a photoconductor cleaning device (an example of a cleaning means) 6T that removes pressure phase transition particles remaining on the surface of the photoconductor 1T after the primary transfer are arranged in this order. The primary transfer roll 5T is arranged inside the intermediate transfer belt 20 and is provided at a position facing the photoconductor 1T.

[0103] Hereinafter, the operation of applying pressure phase transition particles onto the recording medium P and forming an image area will be described while taking the operation of the unit 10T as an example. First, the surface of the photoconductor 1T is charged by the charging roll 2T. The charged surface of the photoconductor 1T is irradiated with a laser beam by the exposure device 3T in accordance with image data sent from a control unit (not shown). As a result, an electrostatic charge image that becomes the application area of ​​the pressure phase transition particles is formed on the surface of the photoconductor 1T.

[0104] The electrostatic image formed on the photoconductor 1T rotates to a development position as the photoconductor 1T travels. At the development position, the electrostatic image on the photoconductor 1T is developed by a developing device 4T and becomes a pressure phase transition particle region.

[0105] The developing device 4T contains a developer containing at least pressure phase transition particles and a carrier. The pressure phase transition particles are triboelectrically charged by being stirred together with the carrier inside the developing device 4T, and are held on a developer roll. As the surface of the photoconductor 1T passes through the developing device 4T, the pressure phase transition particles electrostatically adhere to the electrostatic charge image on the surface of the photoconductor 1T, and the electrostatic charge image is developed by the pressure phase transition particles, forming a pressure phase transition particle region. The photoconductor 1T with the pressure phase transition particle region formed thereon continues to travel, and the pressure phase transition particle region formed on the photoconductor 1T is transported to the primary transfer position.

[0106] When the pressure phase transition particle region on the photoreceptor 1T is transported to the primary transfer position, a primary transfer bias is applied to the primary transfer roll 5T, and an electrostatic force from the photoreceptor 1T toward the primary transfer roll 5T acts on the pressure phase transition particle region, causing the pressure phase transition particle region on the photoreceptor 1T to be transferred onto the intermediate transfer belt 20. The pressure phase transition particles remaining on the photoreceptor 1T are removed and collected by the photoreceptor cleaning device 6T. The photoreceptor cleaning device 6T is, for example, a cleaning blade or a cleaning brush, and is preferably a cleaning brush.

[0107] In units 10Y, 10M, 10C, and 10K, the same operation as in unit 10T is performed using a developer containing color toner. The intermediate transfer belt 20 to which the pressure phase transition particle region has been transferred in unit 10T passes through units 10Y, 10M, 10C, and 10K in sequence, and the toner images of each color are transferred onto the intermediate transfer belt 20 in multiple layers.

[0108] The intermediate transfer belt 20 onto which the pressure phase transition particle region and the four toner images have been transferred in multiple layers through the units 10T, 10Y, 10M, 10C, and 10K reaches a secondary transfer section that includes the intermediate transfer belt 20, an opposing roll 24 that contacts the inner surface of the intermediate transfer belt, and a secondary transfer roll (an example of a secondary transfer means) 26 that is arranged on the image bearing surface side of the intermediate transfer belt 20. Meanwhile, a recording medium P is fed into the gap between the secondary transfer roll 26 and the intermediate transfer belt 20 via a supply mechanism, and a secondary transfer bias is applied to the opposing roll 24. At this time, an electrostatic force from the intermediate transfer belt 20 toward the recording medium P acts on the pressure phase transition particle region and the toner image, and the pressure phase transition particle region and the toner image on the intermediate transfer belt 20 are transferred onto the recording medium P.

[0109] The recording medium P to which the pressure phase transition particle region and the toner image have been transferred is transported to a heating device (an example of a particle heating means) 28, which is an example of a fixing section. By being heated by the heating device 28, the colored toner image is thermally fixed onto the recording medium P, and the pressure phase transition particle region is heated, accelerating the plasticization of the pressure phase transition particles. It is preferable that the heating device 28 is a device that applies heat and pressure (also referred to as a heating and pressure device) from the viewpoint of preventing the pressure phase transition particles from falling off the recording medium P, improving the fixability of the colored toner to the recording medium P, and promoting the plasticization of the pressure phase transition particles. When the heating device 28 is a heating and pressurizing device, it is preferable that the heating device 28 is equipped with a heat source such as a halogen heater and includes a pair of rolls that come into contact with and heat the pressure phase transition particle region and the toner image on the recording medium P. When the recording medium having the pressure phase transition particle region and the toner image passes between the pair of rolls, the colored toner image is thermally fixed onto the recording medium P, and the pressure phase transition particle region is heated, accelerating the plasticization of the pressure phase transition particles.

[0110] In this manner, the recording medium P passes through the printing means 300, and becomes a post-application recording medium P4 on which an image portion is formed and pressure-induced phase transition particles are applied. Next, after application of the toner, the recording medium P4 is transported towards the pressing means 200.

[0111] In the printing system according to this embodiment, the printing means 300 and the pressing means 200 may be disposed close to each other or separated from each other. When the printing means 300 and the pressing means 200 are separated from each other, the printing means 300 and the pressing means 200 are connected by, for example, a conveying means (for example, a belt conveyer) that conveys the recording medium P4 after application.

[0112] The bonding means 200 shown in Figure 3, like the bonding means 200 shown in Figure 2, is equipped with a folding device 220 and a pressure device 230, and is a means for bonding the laminate P5 obtained by folding the recording medium P4 after application, to obtain a bonded printed matter P6. As the pressing means 200 in the printed matter production system shown in FIG. 3, the same pressing means as the pressing means 200 in the printed matter production system shown in FIG. 2 is used.

[0113] <Pressure Phase Change Layer and Pressure Phase Change Particles> The pressure-induced phase change layer and the pressure-induced phase change particles according to this embodiment will be described in detail below. Since the pressure-induced phase change layer according to this embodiment is a layer formed by the pressure-induced phase change particles according to this embodiment, only the pressure-induced phase change particles according to this embodiment will be described below.

[0114] The pressure-induced phase transition particles according to this embodiment contain at least base particles, and may contain an external additive as necessary. The base particles contained in the pressure-induced phase transition particles preferably have at least two glass transition points, with the difference between the lowest and highest glass transition temperatures being 30° C. or more.

[0115] [Mother particle] (Binding resin) The base particles preferably contain, as binder resins, a styrene-based resin containing styrene and other vinyl monomers as polymerization components, and a (meth)acrylic acid ester-based resin containing at least two types of (meth)acrylic acid esters as polymerization components, with the mass ratio of the (meth)acrylic acid esters to the total polymerization components being 90 mass% or more. Hereinafter, "a styrene-based resin containing styrene and other vinyl monomers as polymerization components" is also referred to as "a specific styrene-based resin", and "a (meth)acrylic acid ester-based resin containing at least two types of (meth)acrylic acid esters as polymerization components, in which the mass ratio of (meth)acrylic acid esters in the total polymerization components is 90 mass% or more" is also referred to as "a specific (meth)acrylic acid ester-based resin".

[0116] From the viewpoint of maintaining the compression bonding property by compression bonding, the base particles preferably have a specific styrene resin content greater than the specific (meth)acrylic acid ester resin content. The specific styrene resin content is preferably 55% by mass or more and 80% by mass or less, more preferably 60% by mass or more and 75% by mass or less, and even more preferably 65% ​​by mass or more and 70% by mass or less, based on the total content of the specific styrene resin and the specific (meth)acrylic acid ester resin.

[0117] -Specific styrene resin- The base particles constituting the pressure-induced phase transition particles contain a specific styrene-based resin that contains styrene and other vinyl monomers as polymerization components.

[0118] The mass proportion of styrene in the total polymerization components of the specific styrene-based resin is preferably 60 mass% or more, more preferably 70 mass% or more, and even more preferably 75 mass% or more, from the viewpoint of suppressing fluidization of the pressure-induced phase transition particles in an unpressurized state. The mass proportion of styrene in all the polymerization components of the specific styrene-based resin is preferably 95 mass% or less, more preferably 90 mass% or less, and even more preferably 85 mass% or less, from the viewpoint of forming pressure-induced phase transition particles that easily undergo phase transition due to pressure. That is, the mass proportion of styrene in the total polymerization components of the specific styrene-based resin is preferably 60 mass % or more and 95 mass % or less.

[0119] Examples of vinyl monomers other than styrene contained in the polymerization components of the specific styrene-based resin (hereinafter also referred to as other vinyl monomers) include styrene-based monomers and acrylic-based monomers.

[0120] Examples of styrene-based monomers in the other vinyl monomers include vinylnaphthalene; alkyl-substituted styrenes such as α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, pn-butylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, and pn-dodecylstyrene; aryl-substituted styrenes such as p-phenylstyrene; alkoxy-substituted styrenes such as p-methoxystyrene; halogen-substituted styrenes such as p-chlorostyrene, 3,4-dichlorostyrene, p-fluorostyrene, and 2,5-difluorostyrene; and nitro-substituted styrenes such as m-nitrostyrene, o-nitrostyrene, and p-nitrostyrene. These styrene-based monomers may be used alone or in combination of two or more.

[0121] The acrylic monomer in the other vinyl monomer is preferably at least one acrylic monomer selected from the group consisting of (meth)acrylic acid and (meth)acrylic acid esters. Examples of the (meth)acrylic acid esters include (meth)acrylic acid alkyl esters, (meth)acrylic acid carboxy-substituted alkyl esters, (meth)acrylic acid hydroxy-substituted alkyl esters, (meth)acrylic acid alkoxy-substituted alkyl esters, and di(meth)acrylic acid esters. These acrylic monomers may be used alone or in combination of two or more.

[0122] Examples of (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and isobornyl (meth)acrylate. Examples of the (meth)acrylic acid carboxy-substituted alkyl ester include 2-carboxyethyl (meth)acrylate. Examples of the hydroxy-substituted alkyl (meth)acrylate include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Examples of the alkoxy-substituted alkyl (meth)acrylate esters include 2-methoxyethyl (meth)acrylate. Examples of di(meth)acrylic acid esters include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, pentanediol di(meth)acrylate, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, and decanediol di(meth)acrylate.

[0123] Examples of the (meth)acrylic acid ester include 2-(diethylamino)ethyl (meth)acrylate, benzyl (meth)acrylate, and methoxypolyethylene glycol (meth)acrylate.

[0124] Examples of other vinyl monomers contained in the polymerization components of the specific styrene-based resin include, in addition to styrene-based monomers and acrylic-based monomers, (meth)acrylonitrile; vinyl ethers such as vinyl methyl ether and vinyl isobutyl ether; vinyl ketones such as vinyl methyl ketone, vinyl ethyl ketone and vinyl isopropenyl ketone; and olefins such as isoprene, butene and butadiene.

[0125] From the viewpoint of forming pressure-induced phase transition particles that easily undergo phase transition due to pressure, the specific styrene-based resin preferably contains other vinyl monomers contained as polymerization components that contain a (meth)acrylic acid ester, more preferably a (meth)acrylic acid alkyl ester, even more preferably a (meth)acrylic acid alkyl ester having an alkyl group with 2 to 10 carbon atoms, and even more preferably a (meth)acrylic acid alkyl ester having an alkyl group with 4 to 8 carbon atoms. From the viewpoint of forming pressure-induced phase transition particles that easily undergo a phase transition due to pressure, it is particularly preferable that the other vinyl monomer contained as a polymerization component of the specific styrene-based resin contains at least one of n-butyl acrylate and 2-ethylhexyl acrylate. From the viewpoint of forming pressure-induced phase transition particles which easily undergo a phase transition due to pressure, the specific styrene-based resin and the specific (meth)acrylic acid ester-based resin described below preferably contain the same type of (meth)acrylic acid ester as a polymerization component.

[0126] The mass ratio of the (meth)acrylic acid ester in the entire polymerization components of the specific styrene-based resin is preferably 40% by mass or less, more preferably 30% by mass or less, and even more preferably 25% by mass or less from the viewpoint of suppressing fluidization of pressure-induced phase transition particles in a non-pressurized state, and is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more from the viewpoint of forming pressure-induced phase transition particles that are easy to undergo phase transition by pressure. As the (meth)acrylic acid ester here, a (meth)acrylic acid alkyl ester is preferred, a (meth)acrylic acid alkyl ester having 2 to 10 carbon atoms in the alkyl group is more preferred, and a (meth)acrylic acid alkyl ester having 4 to 8 carbon atoms in the alkyl group is even more preferred.

[0127] It is particularly preferable that the specific styrene-based resin contains at least one of n-butyl acrylate and 2-ethylhexyl acrylate as a polymerization component, and the total amount of n-butyl acrylate and 2-ethylhexyl acrylate in all the polymerization components of the styrene-based resin is preferably 40 mass% or less, more preferably 30 mass% or less, and even more preferably 25 mass% or less, from the viewpoint of suppressing fluidization of the particles in an unpressurized state, and is preferably 5 mass% or more, more preferably 10 mass% or more, and even more preferably 15 mass% or more, from the viewpoint of forming pressure-phase transition particles that are prone to phase transition due to pressure.

[0128] The weight average molecular weight of the specific styrene-based resin is preferably 3,000 or more, more preferably 4,000 or more, and even more preferably 5,000 or more, from the viewpoint of preventing the pressure-induced phase transition particles from fluidizing when no pressure is applied, and is preferably 60,000 or less, more preferably 55,000 or less, and even more preferably 50,000 or less, from the viewpoint of forming pressure-induced phase transition particles that are prone to phase transition when subjected to pressure.

[0129] The weight average molecular weight of the resin is measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC is performed using a Tosoh HLC-8120GPC as the GPC device, a Tosoh TSKgel SuperHM-M (15 cm) as the column, and tetrahydrofuran as the solvent. The weight average molecular weight of the resin is calculated using a molecular weight calibration curve created using monodisperse polystyrene standard samples.

[0130] The glass transition temperature of the specific styrene-based resin is preferably 30°C or higher, more preferably 40°C or higher, and even more preferably 50°C or higher, from the viewpoint of preventing the pressure-induced phase transition particles from fluidizing in an unpressurized state; and is preferably 110°C or lower, more preferably 100°C or lower, and even more preferably 90°C or lower, from the viewpoint of forming pressure-induced phase transition particles that are prone to undergo phase transition when subjected to pressure.

[0131] The glass transition temperature of a resin is determined from a differential scanning calorimetry (DSC) curve obtained by performing differential scanning calorimetry (DSC). More specifically, it is determined according to the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0132] The glass transition temperature of a resin is controlled by the type and polymerization ratio of the polymerization components. The higher the density of flexible units such as methylene groups, ethylene groups, and oxyethylene groups contained in the main chain, the lower the glass transition temperature tends to be, and the higher the density of rigid units such as aromatic rings and cyclohexane rings contained in the main chain, the higher the glass transition temperature tends to be. In addition, the higher the density of aliphatic groups in the side chain, the lower the glass transition temperature tends to be.

[0133] The mass proportion of the specific styrene-based resin in the entire base particle is preferably 55 mass% or more, more preferably 60 mass% or more, and even more preferably 65 mass% or more, from the viewpoint of suppressing fluidization of the pressure-induced phase transition particles in an unpressurized state, and is preferably 80 mass% or less, more preferably 75 mass% or less, and even more preferably 70 mass% or less, from the viewpoint of forming pressure-induced phase transition particles that are prone to phase transition under pressure.

[0134] -Specific (meth)acrylic ester resin- The base particles constituting the pressure-induced phase transition particles preferably contain a (meth)acrylic acid ester-based resin that contains at least two types of (meth)acrylic acid esters as polymerization components, and in which the mass ratio of the (meth)acrylic acid esters to the total polymerization components is 90 mass% or more.

[0135] The mass proportion of (meth)acrylic acid ester in all the polymerization components of the (meth)acrylic acid ester resin is 90 mass % or more, more preferably 95 mass % or more, even more preferably 98 mass % or more, and still more preferably 100 mass %.

[0136] Examples of the (meth)acrylic acid ester include (meth)acrylic acid alkyl ester, (meth)acrylic acid carboxy-substituted alkyl ester, (meth)acrylic acid hydroxy-substituted alkyl ester, (meth)acrylic acid alkoxy-substituted alkyl ester, and di(meth)acrylic acid ester.

[0137] Examples of (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and isobornyl (meth)acrylate. Examples of the (meth)acrylic acid carboxy-substituted alkyl ester include 2-carboxyethyl (meth)acrylate. Examples of the hydroxy-substituted alkyl (meth)acrylate include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Examples of the alkoxy-substituted alkyl (meth)acrylate esters include 2-methoxyethyl (meth)acrylate. Examples of di(meth)acrylic acid esters include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, pentanediol di(meth)acrylate, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, and decanediol di(meth)acrylate.

[0138] Examples of the (meth)acrylic acid ester include 2-(diethylamino)ethyl (meth)acrylate, benzyl (meth)acrylate, and methoxypolyethylene glycol (meth)acrylate.

[0139] The (meth)acrylic acid ester may be used alone or in combination of two or more kinds.

[0140] As the (meth)acrylic acid ester, from the viewpoint of forming pressure-induced phase transition particles that easily undergo phase transition due to pressure and have excellent compression adhesion upon compression, preferred are (meth)acrylic acid alkyl esters, more preferred are (meth)acrylic acid alkyl esters having an alkyl group with 2 to 10 carbon atoms, even more preferred are (meth)acrylic acid alkyl esters having an alkyl group with 4 to 8 carbon atoms, and particularly preferred are n-butyl acrylate and 2-ethylhexyl acrylate. As described above, from the viewpoint of forming pressure-induced phase transition particles that easily undergo phase transition due to pressure, the specific (meth)acrylic acid ester-based resin and the specific styrene-based resin preferably contain the same type of (meth)acrylic acid ester as a polymerization component.

[0141] The mass ratio of the (meth)acrylic acid alkyl ester to the entire polymerization components of the specific (meth)acrylic acid ester resin is preferably 90 mass% or more, more preferably 95 mass% or more, even more preferably 98 mass% or more, and even more preferably 100 mass% from the viewpoint of forming pressure-induced phase transition particles that are easy to undergo phase transition by pressure and have excellent compression bonding properties by compression bonding. As the (meth)acrylic acid alkyl ester here, a (meth)acrylic acid alkyl ester having an alkyl group with 2 to 10 carbon atoms is preferable, and a (meth)acrylic acid alkyl ester having an alkyl group with 4 to 8 carbon atoms is more preferable.

[0142] The mass ratio of the two (meth)acrylic esters having the largest mass proportions among the at least two (meth)acrylic esters contained as polymerization components in the specific (meth)acrylic ester-based resin is preferably 80:20 to 20:80, more preferably 70:30 to 30:70, and even more preferably 60:40 to 40:60, from the viewpoint of forming pressure-induced phase transition particles that are easily subjected to phase transition by pressure and have excellent compression bonding properties.

[0143] Of the at least two (meth)acrylic esters contained as polymerization components in the specific (meth)acrylic ester-based resin, the two with the largest mass ratios are preferably (meth)acrylic acid alkyl esters. The (meth)acrylic acid alkyl esters herein are preferably (meth)acrylic acid alkyl esters having an alkyl group with 2 to 10 carbon atoms, and more preferably (meth)acrylic acid alkyl esters having an alkyl group with 4 to 8 carbon atoms.

[0144] When the two (meth)acrylic acid esters having the largest mass proportions among the at least two (meth)acrylic acid esters contained as polymerization components in the specific (meth)acrylic acid ester-based resin are (meth)acrylic acid alkyl esters, the difference in the number of carbon atoms in the alkyl groups of the two (meth)acrylic acid alkyl esters is preferably 1 to 4, more preferably 2 to 4, and even more preferably 3 or 4, from the viewpoint of forming pressure-induced phase transition particles that are easily transitioned by pressure and have excellent compression adhesion upon compression.

[0145] From the viewpoint of forming pressure-induced phase transition particles that easily undergo phase transition under pressure and have excellent compression bonding properties, the specific (meth)acrylic acid ester resin preferably contains n-butyl acrylate and 2-ethylhexyl acrylate as polymerization components, and it is particularly preferable that the two types of (meth)acrylic acid esters that have the largest mass ratios among at least two types of (meth)acrylic acid esters contained as polymerization components in the (meth)acrylic acid ester resin are n-butyl acrylate and 2-ethylhexyl acrylate. The total amount of n-butyl acrylate and 2-ethylhexyl acrylate in the total polymerization components of the (meth)acrylic acid ester resin is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 100% by mass.

[0146] The specific (meth)acrylic acid ester resin may contain a vinyl monomer other than the (meth)acrylic acid ester as a polymerization component. Examples of vinyl monomers other than (meth)acrylic acid esters include (meth)acrylic acid, styrene, styrene-based monomers other than styrene, (meth)acrylonitrile, vinyl ethers such as vinyl methyl ether and vinyl isobutyl ether, vinyl ketones such as vinyl methyl ketone, vinyl ethyl ketone and vinyl isopropenyl ketone, and olefins such as isoprene, butene and butadiene. These vinyl monomers may be used alone or in combination of two or more.

[0147] When the specific (meth)acrylic acid ester resin contains a vinyl monomer other than (meth)acrylic acid ester as a polymerization component, the vinyl monomer other than (meth)acrylic acid ester is preferably at least one of acrylic acid and methacrylic acid, and more preferably acrylic acid.

[0148] The weight average molecular weight of the specific (meth)acrylic acid ester resin is preferably 100,000 or more, more preferably 120,000 or more, and even more preferably 150,000 or more, from the viewpoint of suppressing fluidization of the particles in the absence of pressure, and is preferably 250,000 or less, more preferably 220,000 or less, and even more preferably 200,000 or less, from the viewpoint of forming particles that are prone to phase transition due to pressure.

[0149] The glass transition temperature of the specific (meth)acrylic acid ester resin is preferably 10° C. or lower, more preferably 0° C. or lower, and even more preferably −10° C. or lower, from the viewpoint of forming particles that easily undergo phase transition due to pressure, and is preferably −90° C. or higher, more preferably −80° C. or higher, and even more preferably −70° C. or higher, from the viewpoint of preventing the particles from fluidizing in an unpressurized state.

[0150] The mass proportion of the specific (meth)acrylic acid ester resin in the entire mother particle is preferably 20 mass% or more, more preferably 25 mass% or more, and even more preferably 30 mass% or more, from the viewpoint of forming pressure-phase transition particles that are prone to phase transition due to pressure, and is preferably 45 mass% or less, more preferably 40 mass% or less, and even more preferably 35 mass% or less, from the viewpoint of suppressing fluidization of the particles in an unpressurized state.

[0151] In this embodiment, the total amount of the specific styrene-based resin and the specific (meth)acrylic acid ester-based resin contained in the base particle is preferably 70 mass% or more, more preferably 80 mass% or more, even more preferably 90 mass% or more, even more preferably 95 mass% or more, and even more preferably 100 mass% based on the entire base particle.

[0152] The base particles may contain, as necessary, for example, polystyrene; non-vinyl resins such as epoxy resin, polyester resin, polyurethane resin, polyamide resin, cellulose resin, polyether resin, and modified rosin; and the like. These resins may be used alone or in combination of two or more.

[0153] (Other Ingredients) The base particles may contain other components as necessary. Other components include colorants (e.g., pigments, dyes), release agents (e.g., hydrocarbon waxes; natural waxes such as carnauba wax, rice wax, candelilla wax, etc.; synthetic or mineral / petroleum waxes such as montan wax; ester waxes such as fatty acid esters, montan acid esters, etc.), and charge control agents.

[0154] The pressure-induced phase transition particles may contain a colorant as long as the colorant does not impair the visibility of the image. The content of the colorant in the base particle is preferably as small as possible in order to enhance the transparency of the pressure-induced phase transition particle. Specifically, the content of the colorant is preferably 1.0% by mass or less, more preferably 0.1% by mass or less, and even more preferably 0.01% by mass or less, based on the total mass of the base particle, and is particularly preferably zero.

[0155] The pressure-induced phase transition particles may be transparent. In this embodiment, "transparent" means that the area to which the pressure-induced phase transition particles are applied has an average light transmittance in the visible range (400 nm or more and 700 nm or less) of 10% or more, preferably 50% or more, more preferably 80% or more, and even more preferably 90% or more. The average transmittance is measured using a spectrophotometer V700 (manufactured by JASCO Corporation).

[0156] (Structure of host particles) The internal structure of the base particle is preferably an island-in-a-sea structure. The sea-island structure is preferably a sea-island structure having a sea phase containing one of two or more binder resins and an island phase containing the other of the two or more binder resins dispersed in the sea phase. More specifically, from the viewpoint of facilitating phase transition by pressure, a sea-island structure is preferably a sea phase containing a specific styrene-based resin and an island phase containing a specific (meth)acrylic acid ester-based resin dispersed in the sea phase. Details of the specific styrene-based resin contained in the sea phase and the (meth)acrylic acid ester-based resin contained in the island phase are as described above. Note that an island phase not containing a (meth)acrylic acid ester-based resin may be dispersed in the sea phase.

[0157] When the base particles have a sea-island structure, the average diameter of the island phase is preferably 200 nm or more and 500 nm or less. When the average diameter of the island phase is 500 nm or less, the base particles are easily subjected to phase transition due to pressure, and when the average diameter of the island phase is 200 nm or more, the base particles have excellent mechanical strength (e.g., strength that makes it difficult to deform when stirred in a developer). From these viewpoints, the average diameter of the island phase is more preferably 220 nm or more and 450 nm or less, and even more preferably 250 nm or more and 400 nm or less.

[0158] Methods for controlling the average diameter of the island phases in the sea-island structure within the above range include, for example, increasing or decreasing the amount of the specific (meth)acrylic ester resin relative to the amount of the specific styrene resin in the method for producing base particles described below, and increasing or decreasing the time for which the high temperature is maintained in the step of fusing and coalescing the aggregated resin particles.

[0159] The sea-island structure and the average diameter of the island phase are determined by the following method. The pressure-induced phase transition particles are embedded in epoxy resin, sliced ​​using a diamond knife or similar, and stained with osmium tetroxide or ruthenium tetroxide in a desiccator. The stained slices are observed under a scanning electron microscope (SEM). The sea phase and island phase of the sea-island structure are distinguished by the shade of the resin stained by osmium tetroxide or ruthenium tetroxide, and this is used to confirm the presence or absence of a sea-island structure. 100 island phases are randomly selected from the SEM image, and the long diameter of each island phase is measured, and the average of the long diameters of the 100 islands is taken as the average diameter.

[0160] The base particles may be base particles of a single layer structure, or base particles of a core-shell structure having a core and a shell layer covering the core. From the viewpoint of suppressing fluidization of the pressure-induced phase transition particles in an unpressurized state, the base particles preferably have a core-shell structure.

[0161] When the base particle has a core-shell structure, the core preferably contains a specific styrene resin and a specific (meth)acrylic acid ester resin from the viewpoint of facilitating pressure-induced phase transition.Furthermore, the shell preferably contains a specific styrene resin from the viewpoint of preventing the pressure-induced phase transition particles from fluidizing in a non-pressurized state.

[0162] When the base particle has a core-shell structure, the core preferably has a sea phase containing a specific styrene resin and an island phase containing a specific (meth)acrylic acid ester resin dispersed in the sea phase. The average diameter of the island phase is preferably within the above-mentioned range. Furthermore, in addition to the above-mentioned core structure, the shell layer preferably contains a specific styrene resin. In this case, the sea phase and the shell layer of the core are in a continuous structure, and the base particle is easily subjected to phase transition due to pressure.

[0163] Examples of the resin contained in the shell layer include polystyrene; and non-vinyl resins such as epoxy resin, polyester resin, polyurethane resin, polyamide resin, cellulose resin, polyether resin, and modified rosin. These resins may be used alone or in combination of two or more.

[0164] From the viewpoint of suppressing deformation of the base particles, the average thickness of the shell layer is preferably 120 nm or more, more preferably 130 nm or more, and even more preferably 140 nm or more, and from the viewpoint of facilitating phase transition of the base particles due to pressure, the average thickness of the shell layer is preferably 550 nm or less, more preferably 500 nm or less, and even more preferably 400 nm or less.

[0165] The average thickness of the shell layer is measured by the following method. The particles are embedded in epoxy resin, sliced ​​using a diamond knife or similar, and stained with osmium tetroxide or ruthenium tetroxide in a desiccator. The stained slices are observed under a scanning electron microscope (SEM). Ten mother particle cross sections are randomly selected from the SEM images, and the shell layer thickness is measured at 20 points on each mother particle, the average value is calculated, and the average value of the 10 mother particles is taken as the average thickness.

[0166] From the viewpoint of ease of handling of the mother particles, the volume average particle size (D50v) of the mother particles is preferably 4 μm or more, more preferably 5 μm or more, and even more preferably 6 μm or more, and is preferably 15 μm or less, more preferably 12 μm or less, and even more preferably 10 μm or less.

[0167] The volume average particle size (D50v) of the parent particles is measured using a Coulter Multisizer II (Beckman Coulter, Inc.) with an aperture of 100 μm diameter. 0.5 mg to 50 mg of parent particles are added and dispersed in 2 mL of 5 mass% aqueous solution of sodium alkylbenzene sulfonate, then mixed with 100 mL to 150 mL of electrolyte (ISOTON-II, Beckman Coulter, Inc.), dispersed for 1 minute with an ultrasonic disperser, and the resulting dispersion is used as the sample. The particle size of 50,000 particles with a particle size of 2 μm to 60 μm in the sample is measured. The particle size at which the cumulative 50% of the particle size distribution on a volume basis calculated from the small diameter side is the volume average particle size (D50v).

[0168] [External additives] The external additive may be, for example, inorganic particles. Examples of inorganic particles include SiO 2 , TiO 2 , Al 2 O 3 , CuO, ZnO, SnO 2 , CEO 2 , Fe 2 O 3 , MgO, BaO, CaO, K 2 O, Na 2 O, ZrO 2 , CaO SiO 2 , K2 O (TiO 2 )n, Al 2 O 3 2SiO 2 , CaCO 3 , MgCO 3 , BaSO 4 , MgSO 4 etc.

[0169] The surface of the inorganic particles as an external additive may be hydrophobized. The hydrophobization may be performed, for example, by immersing the inorganic particles in a hydrophobizing agent. The hydrophobizing agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobizing agent is, for example, 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the inorganic particles.

[0170] Examples of external additives include resin particles (resin particles such as polystyrene, polymethyl methacrylate, and melamine resin), cleaning agents (for example, metal salts of higher fatty acids such as zinc stearate, and fluorine-based polymer particles), and the like.

[0171] The amount of the external additive added is preferably from 0.01% by mass to 5% by mass, and more preferably from 0.01% by mass to 2.0% by mass, based on the base particles.

[0172] [Characteristics of Pressure Phase Change Particles] The pressure phase transition particles have at least two glass transition temperatures, one of which is presumed to be a glass transition temperature derived from one of two or more binder resins, and the other is presumed to be a glass transition temperature derived from the other of the two or more binder resins. As described above, when the binder resin contains a specific styrene-based resin and a specific (meth)acrylic acid ester-based resin, one of the glass transition temperatures is presumed to be a glass transition temperature of the specific styrene-based resin, and the other is presumed to be a glass transition temperature of the specific (meth)acrylic acid ester-based resin.

[0173] The pressure-induced phase transition particles may have three or more glass transition temperatures, but the number of glass transition temperatures is preferably 2. The pressure-induced phase transition particles having two glass transition temperatures include those in which the resins contained in the pressure-induced phase transition particles are only the specific styrene-based resin and the specific (meth)acrylic acid ester-based resin, and those in which the content of other resins other than the specific styrene-based resin and the specific (meth)acrylic acid ester-based resin is small (for example, the content of other resins is 5% by mass or less relative to the entire pressure-induced phase transition particles).

[0174] The pressure-induced phase transition particles have at least two glass transition temperatures, and the difference between the lowest glass transition temperature and the highest glass transition temperature is 30° C. or more. From the viewpoint of facilitating phase transition of the particles by pressure, the difference between the lowest glass transition temperature and the highest glass transition temperature is more preferably 40° C. or more, even more preferably 50° C. or more, and even more preferably 60° C. or more. The upper limit of the difference between the lowest glass transition temperature and the highest glass transition temperature is, for example, 140° C. or less, 130° C. or less, or 120° C. or less.

[0175] The lowest glass transition temperature exhibited by the pressure-induced phase transition particles is preferably 10°C or lower, more preferably 0°C or lower, and even more preferably -10°C or lower, from the viewpoint of making the particles prone to phase transition due to pressure, and is preferably -90°C or higher, more preferably -80°C or higher, and even more preferably -70°C or higher, from the viewpoint of preventing the particles from fluidizing in an unpressurized state.

[0176] The highest glass transition temperature exhibited by the pressure-induced phase transition particles is preferably 30°C or higher, more preferably 40°C or higher, and even more preferably 50°C or higher, from the viewpoint of preventing the particles from fluidizing in the absence of pressure, and is preferably 70°C or lower, more preferably 65°C or lower, and even more preferably 60°C or lower, from the viewpoint of facilitating phase transition of the particles due to pressure.

[0177] The glass transition temperature of the pressure-induced phase transition particle is determined from a differential scanning calorimetry (DSC) curve obtained by compressing the pressure-induced phase transition particle to prepare a plate-shaped sample and performing differential scanning calorimetry (DSC). More specifically, the glass transition temperature is determined according to the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0178] The pressure-induced phase transition particles are particles that undergo a phase transition due to pressure and satisfy the following formula 1. Formula 1...10℃≦T1-T2 In formula 1, T1 is the temperature at which the viscosity is 10,000 Pa s under a pressure of 1 MPa, and T2 is the temperature at which the viscosity is 10,000 Pa s under a pressure of 10 MPa. How to determine T1 and T2 will be described later.

[0179] The temperature difference (T1-T2) is preferably 10°C or more, more preferably 15°C or more, and even more preferably 20°C or more, from the viewpoint of facilitating phase transition of the particles due to pressure, and is preferably 120°C or less, more preferably 100°C or less, and even more preferably 80°C or less, from the viewpoint of preventing the pressure-induced phase transition particles from fluidizing in an unpressurized state.

[0180] The value of T1 is preferably 140° C. or less, more preferably 130° C. or less, even more preferably 120° C. or less, and still more preferably 115° C. or less. The lower limit of the temperature T1 is preferably 80° C. or more, and more preferably 85° C. or more. The value of T2 is preferably 40° C. or more, more preferably 50° C. or more, and even more preferably 60° C. or more. The upper limit of the temperature T2 is preferably 85° C. or less.

[0181] An index showing that pressure-induced phase transition particles are susceptible to phase transition due to pressure is the temperature difference (T1-T3) between the temperature T1 at which the particle has a viscosity of 10,000 Pa·s under a pressure of 1 MPa and the temperature T3 at which the particle has a viscosity of 10,000 Pa·s under a pressure of 4 MPa. It is preferable that the temperature difference (T1-T3) is 5°C or more. 1 -T 2) is generally below 25°C. Pressure phase transition particles are characterized by the fact that they undergo phase transitions easily when subjected to pressure. 1 -T 2 ) is preferably 5°C or higher, and more preferably 10°C or higher. The upper limit of the temperature difference (T1-T3) is generally 25°C or less.

[0182] From the viewpoint of a temperature difference (T1-T3) of 5° C. or more, the pressure-induced phase transition particle has a temperature T3 at which it exhibits a viscosity of 10,000 Pa s under a pressure of 4 MPa of preferably 90° C. or less, more preferably 85° C. or less, and even more preferably 80° C. or less. The lower limit of the temperature T3 is preferably 60° C. or more.

[0183] The temperature T1, the temperature T2, and the temperature T3 are calculated as follows. The pressure-induced phase transition particles are compressed to prepare a pellet-shaped sample. The pellet-shaped sample is set in a flow tester (Shimadzu Corporation, CFT-500), and the applied pressure is fixed at 1 MPa, and the viscosity at 1 MPa versus temperature is measured. From the obtained viscosity graph, it is found that the viscosity is 10 4 Determine the temperature T1 when the pressure becomes Pa·s. Determine the temperature T2 in the same manner as for temperature T1, except that the applied pressure of 1 MPa is changed to 10 MPa. Determine the temperature T3 in the same manner as for temperature T1, except that the applied pressure of 1 MPa is changed to 4 MPa. Calculate the temperature difference (T1-T2) from temperatures T1 and T2. Calculate the temperature difference (T1-T3) from temperatures T1 and T3.

[0184] [Method for producing pressure phase transition particles] The pressure-induced phase transition particles can be obtained by producing base particles and then externally adding an external additive to the base particles.

[0185] The base particles may be produced by any of a dry production method (e.g., a kneading and grinding method, etc.) and a wet production method (e.g., an aggregation and coalescence method, a suspension polymerization method, a dissolution suspension method, etc.). There are no particular limitations on these production methods, and any known production method may be used. Among these, it is preferable to obtain the base particles by the aggregation and coalescence method.

[0186] Hereinafter, a method for producing base particles by the aggregation-coalescence method will be described as an example. When the base particles are produced by the aggregation and coalescence method, for example, A step of preparing a styrene-based resin particle dispersion liquid in which styrene-based resin particles containing a specific styrene-based resin are dispersed (a styrene-based resin particle dispersion liquid preparation step); a step of polymerizing a specific (meth)acrylic acid ester-based resin in a styrene-based resin particle dispersion to form composite resin particles containing the specific styrene-based resin and the specific (meth)acrylic acid ester-based resin (composite resin particle forming step); a step of aggregating the composite resin particles in the composite resin particle dispersion liquid in which the composite resin particles are dispersed to form aggregated particles (aggregated particle forming step); The aggregated particle dispersion liquid in which the aggregated particles are dispersed is heated to fuse and coalesce the aggregated particles to form mother particles (fusion and coalescence step), and the mother particles are produced through this process.

[0187] Each step will be described in detail below. In the following, a method for obtaining base particles that do not contain a release agent will be described. A release agent and other additives may be used as necessary. When the base particles contain a colorant and / or a release agent, in the aggregated particle formation step, a colorant particle dispersion and / or a release agent particle dispersion are mixed with the composite resin particle dispersion to aggregate the composite resin particles with the colorant and / or the release agent to form aggregated particles. The colorant particle dispersion liquid and the release agent particle dispersion liquid are prepared, for example, by mixing a colorant or a release agent with a dispersion medium, and then performing a dispersion treatment using a known dispersing machine.

[0188] - Preparation process of styrene-based resin particle dispersion - In the styrene-based resin particle dispersion preparation step, a styrene-based resin particle dispersion in which styrene-based resin particles containing a specific styrene-based resin are dispersed is prepared. The styrene-based resin particle dispersion liquid is, for example, a dispersion liquid in which styrene-based resin particles are dispersed in a dispersion medium by the aid of a surfactant.

[0189] Examples of the dispersion medium include aqueous media such as water, alcohols, etc. These may be used alone or in combination of two or more.

[0190] Examples of the surfactant include anionic surfactants such as sulfate salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. The nonionic surfactants may be used in combination with anionic surfactants or cationic surfactants. Among these, anionic surfactants are preferred. The surfactants may be used alone or in combination with two or more.

[0191] Examples of a method for dispersing styrene-based resin particles in a dispersion medium include a method in which a specific styrene-based resin is mixed with a dispersion medium and stirred and dispersed using a rotary shear type homogenizer, a ball mill having media, a sand mill, a dyno mill, or the like.

[0192] Another method for dispersing styrene-based resin particles in a dispersion medium is emulsion polymerization.Specifically, after mixing the polymerization components of specific styrene-based resin with a chain transfer agent or a polymerization initiator, further mix with an aqueous medium containing a surfactant, and stir to prepare an emulsion, and polymerize the styrene-based resin in the emulsion.At this time, it is preferable to use dodecanethiol as a chain transfer agent.

[0193] The volume average particle size of the styrene-based resin particles dispersed in the styrene-based resin particle dispersion is preferably 100 nm or more and 250 nm or less, more preferably 120 nm or more and 220 nm or less, and even more preferably 150 nm or more and 200 nm or less. The volume average particle diameter of the resin particles contained in the resin particle dispersion is measured using a laser diffraction particle size distribution measuring device (e.g., LA-700 manufactured by Horiba, Ltd.), and the particle diameter that is 50% cumulative in the volume-based particle size distribution calculated from the small diameter side is defined as the volume average particle diameter (D50v).

[0194] The content of the styrene-based resin particles in the styrene-based resin particle dispersion is preferably 30% by mass or more and 60% by mass or less, and more preferably 40% by mass or more and 50% by mass or less, based on the total mass of the styrene-based resin particle dispersion.

[0195] -Composite resin particle formation process- In the composite resin particle formation step, a specific (meth)acrylic ester resin is polymerized in a styrene-based resin particle dispersion liquid to form composite resin particles containing the specific styrene-based resin and the specific (meth)acrylic ester resin. In the composite resin particle formation process, a styrene-based resin particle dispersion liquid and a polymerization component of a specific (meth)acrylic acid ester-based resin are mixed, and the specific (meth)acrylic acid ester-based resin is polymerized in the styrene-based resin particle dispersion liquid to form composite resin particles containing the specific styrene-based resin and the specific (meth)acrylic acid ester-based resin.

[0196] The composite resin particles are preferably resin particles containing a specific styrene-based resin and a specific (meth)acrylic acid ester-based resin in a state of microphase separation. The resin particles are produced, for example, by the following method.

[0197] A polymerization component of a specific (meth)acrylic acid ester resin (a group of monomers containing at least two types of (meth)acrylic acid ester) is added to a styrene-based resin particle dispersion, and an aqueous medium is added as necessary. Next, while slowly stirring the dispersion, the temperature of the dispersion is heated to a temperature equal to or higher than the glass transition temperature of the specific styrene-based resin (for example, a temperature 10°C to 30°C higher than the glass transition temperature of the specific styrene-based resin). Next, while maintaining the temperature, an aqueous medium containing a polymerization initiator is slowly dripped, and stirring is continued for a long period of time ranging from 1 hour to 15 hours. At this time, it is preferable to use ammonium persulfate as the polymerization initiator.

[0198] Although the detailed mechanism is not necessarily clear, it is speculated that when the above method is adopted, the monomer and the polymerization initiator are impregnated into the styrene resin particles, and the specific (meth)acrylic acid ester is polymerized inside the styrene resin particles. As a result, it is speculated that a composite resin particle is obtained in which the specific (meth)acrylic acid ester resin is contained inside the styrene resin particles, and the specific styrene resin and the specific (meth)acrylic acid ester resin form a microphase separation state inside the particles.

[0199] The volume average particle size of the composite resin particles dispersed in the composite resin particle dispersion is preferably 140 nm or more and 300 nm or less, more preferably 150 nm or more and 280 nm or less, and even more preferably 160 nm or more and 250 nm or less.

[0200] The content of the composite resin particles in the composite resin particle dispersion is preferably from 20% by mass to 50% by mass, and more preferably from 30% by mass to 40% by mass, based on the total mass of the composite resin particle dispersion.

[0201] -Agglomerated particle formation process- In the aggregated particle forming step, the composite resin particles in the composite resin particle dispersion liquid in which the composite resin particles are dispersed are aggregated to form aggregated particles. Here, in the aggregated particle forming step, the composite resin particles are aggregated to form aggregated particles having a diameter close to that of the target mother particles.

[0202] Specifically, in the aggregated particle formation process, for example, an aggregating agent is added to the composite resin particle dispersion liquid, and the pH of the composite resin particle dispersion liquid is adjusted to be acidic (e.g., pH 2 or more and 5 or less), and if necessary, a dispersion stabilizer is added, and then the mixture is heated to a temperature close to the glass transition temperature of the specific styrene-based resin (specifically, for example, the glass transition temperature of the specific styrene-based resin -30°C or more and the glass transition temperature -10°C or less), to aggregate the composite resin particles and form aggregated particles.

[0203] In the aggregated particle formation process, an aggregating agent is added to the composite resin particle dispersion at room temperature (e.g., 25°C) while stirring the composite resin particle dispersion with a rotary shear homogenizer, the pH of the composite resin particle dispersion is adjusted to an acidic state (e.g., pH 2 or more and 5 or less), and a dispersion stabilizer may be added as necessary, followed by heating.

[0204] Examples of the flocculant include a surfactant having a polarity opposite to that of the surfactant contained in the composite resin particle dispersion, an inorganic metal salt, and a divalent or higher metal complex. When a metal complex is used as the flocculant, the amount of the surfactant used is reduced, and the charging characteristics are improved. If necessary, an additive that forms a complex or a similar bond with the metal ion of the flocculant may be used together with the flocculant. As this additive, a chelating agent is preferably used.

[0205] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. The chelating agent may be a water-soluble chelating agent, for example, oxycarboxylic acid such as tartaric acid, citric acid, gluconic acid, etc., aminocarboxylic acid such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), ethylenediaminetetraacetic acid (EDTA), etc. The amount of the chelating agent added is preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, based on 100 parts by mass of the resin particles.

[0206] -Fusion / coalescence process- In the fusion / coalescence process, the aggregated particle dispersion liquid in which the aggregated particles are dispersed is heated to fuse and coalesce the aggregated particles to form mother particles. In the fusion / coalescence process, the aggregated particle dispersion liquid in which the aggregated particles are dispersed is heated, for example, to a temperature equal to or higher than the glass transition temperature of the specific styrene-based resin (for example, a temperature 10°C to 30°C higher than the glass transition temperature of the specific styrene-based resin) to fuse and coalesce the aggregated particles to form mother particles.

[0207] The base particles obtained through the above steps usually have a sea-island structure having a sea phase containing the specific styrene resin and an island phase containing the specific (meth)acrylic ester resin dispersed in the sea phase. In the composite resin particles, the specific styrene resin and the specific (meth)acrylic ester resin are in a state of microphase separation, and it is presumed that in the fusion / coalescence step, the specific styrene resin comes together to form the sea phase, and the specific (meth)acrylic ester resin comes together to form the island phase.

[0208] The average diameter of the island phases in the sea-island structure can be controlled, for example, by increasing or decreasing the amount of the styrene-based resin particle dispersion or the amount of the at least two kinds of (meth)acrylic acid esters used in the composite resin particle formation step, or by increasing or decreasing the time for which the mixture is maintained at high temperature in the fusion / coalescence step.

[0209] The core-shell structure of the mother particle is, for example, a step of forming second aggregated particles by further mixing the aggregated particle dispersion (hereinafter also referred to as a first aggregated particle dispersion in which the first aggregated particles are dispersed) with a styrene-based resin particle dispersion and aggregating the aggregated particles so that the styrene-based resin particles are further attached to the surfaces of the aggregated particles, and forming second aggregated particles (second aggregated particle forming step); a step of heating the second aggregated particle dispersion liquid in which the second aggregated particles are dispersed to fuse and coalesce the second aggregated particles to form mother particles having a core-shell structure (core-shell structure forming step); It is manufactured through the process. The core-shell structured base particles obtained through the above steps have a shell layer containing a specific styrene-based resin. Instead of the styrene-based resin particle dispersion, a resin particle dispersion in which other types of resin particles are dispersed may be used to form a shell layer containing other types of resin.

[0210] After the fusion and coalescence process is completed, the base particles formed in the liquid are subjected to a known washing process, solid-liquid separation process, and drying process to obtain base particles in a dry state. In the washing step, from the viewpoint of chargeability, it is preferable to carry out sufficient replacement washing with ion-exchanged water. In the solid-liquid separation step, it is preferable to carry out suction filtration, pressure filtration, etc., in terms of productivity. In the drying step, it is preferable to carry out freeze drying, air flow drying, fluidized drying, vibration type fluidized drying, etc., in terms of productivity.

[0211] The pressure-induced phase transition particles are produced, for example, by adding an external additive to the obtained base particles in a dry state and mixing them. The mixing may be carried out, for example, by using a V blender, a Henschel mixer, a Loedige mixer or the like. Furthermore, if necessary, coarse particles may be removed using a vibration sieve, a wind sieve, or the like.

[0212] The pressure-induced phase transition particles may be used as they are by coating, or may be used as an electrostatic image developer. The electrostatic image developer may be a one-component developer containing only pressure-induced phase transition particles, or may be a two-component developer containing a mixture of pressure-induced phase transition particles and a carrier.

[0213] The carrier is not particularly limited, and may be a known carrier. For example, the carrier may be a coated carrier in which the surface of a core material made of magnetic powder is coated with a resin; a magnetic powder dispersion type carrier in which magnetic powder is dispersed and mixed in a matrix resin; a resin impregnated type carrier in which porous magnetic powder is impregnated with a resin; etc. The magnetic powder dispersion type carrier and the resin impregnated type carrier may be a carrier in which the constituent particles of the carrier are used as a core material, and the surface of the core material is coated with a resin.

[0214] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt; magnetic oxides such as ferrite and magnetite; and the like.

[0215] Examples of the resin and matrix resin for coating include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylic acid ester copolymer, straight silicone resin or its modified product containing organosiloxane bonds, fluororesin, polyester, polycarbonate, phenolic resin, epoxy resin, etc. The resin and matrix resin for coating may contain other additives such as conductive particles. Examples of the conductive particles include particles of metals such as gold, silver, copper, carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, potassium titanate, etc.

[0216] Examples of methods for coating the surface of the core material with a resin include a method of coating with a coating layer-forming solution in which the coating resin and various additives (used as necessary) are dissolved in a suitable solvent. The solvent is not particularly limited and may be selected taking into consideration the type of resin used, suitability for application, etc. Specific resin coating methods include an immersion method in which the core material is immersed in a solution for forming a coating layer; a spray method in which the solution for forming a coating layer is sprayed onto the surface of the core material; a fluidized bed method in which the solution for forming a coating layer is sprayed onto the core material while it is suspended in flowing air; and a kneader coater method in which the carrier core material and the solution for forming a coating layer are mixed in a kneader coater and then the solvent is removed.

[0217] The mixing ratio (mass ratio) of pressure phase transition particles and carrier in the two-component developer is preferably particles:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100. EXAMPLES

[0218] Hereinafter, the embodiments of the present invention will be described in detail with reference to examples, but the embodiments of the present invention are not limited to these examples. In the following description, unless otherwise specified, "parts" and "%" are based on mass.

[0219] Example A <Preparation of pressure phase transition particles> [Preparation of styrene-based resin particle dispersion (A1) and composite resin particle dispersion (A1)] Styrene: 450 parts n-Butyl acrylate: 140 parts Acrylic acid: 20 parts Dodecanethiol: 10 parts The above components were mixed and dissolved to prepare a monomer solution. 10 parts of an anionic surfactant (DOWFAX2A1, manufactured by Dow Chemical Company) was dissolved in 250 parts of ion-exchanged water, and the monomer solution was added thereto, and the mixture was dispersed and emulsified in a flask to obtain an emulsion. One part of anionic surfactant (DOWFAX2A1, manufactured by The Dow Chemical Company) was dissolved in 555 parts of ion-exchanged water and charged into a polymerization flask equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube. While injecting nitrogen and slowly stirring, the polymerization flask was heated to 75°C in a water bath and maintained at that temperature. 9 parts of ammonium persulfate was dissolved in 43 parts of ion-exchanged water, and the solution was added to a polymerization flask using a quantitative pump. After the emulsion was added dropwise via a metering pump over 20 minutes, the emulsion was added dropwise via a metering pump over 200 minutes. Thereafter, the polymerization flask was kept at 75° C. for 3 hours with continued stirring, and then returned to room temperature (25° C.) to complete the first stage polymerization. This resulted in a styrene-based resin particle dispersion (A1) containing styrene-based resin particles, the resin particles having a volume average particle size (D50v) of 195 nm, a glass transition temperature of 53° C., and a weight average molecular weight by GPC (UV detection) of 32,000.

[0220] Next, 240 parts of 2-ethylhexyl acrylate, 160 parts of n-butyl acrylate, and 1,200 parts of ion-exchanged water were added to a polymerization flask containing the styrene-based resin particle dispersion (A1) whose temperature had been reduced to room temperature (25°C), and the mixture was slowly stirred for 2 hours. Thereafter, the temperature was raised to 70° C. while continuing stirring, and 4.5 parts of ammonium persulfate and 100 parts of ion-exchanged water were added dropwise over 20 minutes via a metering pump. Thereafter, the mixture was maintained for 3 hours while continuing stirring to complete the polymerization. Through the above steps, a composite resin particle dispersion (A1) was obtained with a volume average particle size (D50v) of 240 nm, a weight average molecular weight measured by GPC (UV detection) of 133,000, a number average molecular weight of 18,000, and a solid content of 30 mass% adjusted by adding ion-exchanged water.

[0221] The composite resin particles of the obtained composite resin particle dispersion (A1) were dried, and the dried composite resin particles were embedded in epoxy resin to prepare a sample. The sample was then cut with a diamond knife to prepare a cross-sectional slice of the composite resin particle. The cut surface of the sample was stained in ruthenium tetroxide vapor, and then observed with a transmission electron microscope. As a result of the cross-sectional observation of the composite resin particle, it was confirmed that the composite resin particle had a structure in which multiple domains of low Tg (meth)acrylic acid ester resin were dispersed in a high Tg styrene resin as a base material. When the glass transition temperature (Tg) behavior of the dried composite resin particles was analyzed from -150°C using a Shimadzu Corporation differential scanning calorimeter (DSC), a glass transition due to the low Tg (meth)acrylic ester resin was observed at -60°C. Also, a glass transition due to the high Tg styrene resin was observed at 53°C (glass transition temperature difference: 113°C).

[0222] [Preparation of styrene-based resin particle dispersion (B1)] Styrene: 450 parts n-Butyl acrylate: 135 parts Acrylic acid: 12 parts Dodecanethiol: 9 parts The above components were mixed and dissolved to prepare a monomer solution. On the other hand, 10 parts of an anionic surfactant (DOWFAX2A1, manufactured by Dow Chemical Company) was dissolved in 250 parts of ion-exchanged water, and the monomer solution was added thereto, and the mixture was dispersed and emulsified in a flask to obtain an emulsion. One part of anionic surfactant (DOWFAX2A1, manufactured by Dow Chemical Company) was dissolved in 555 parts of ion-exchanged water and charged into a polymerization flask equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube. While injecting nitrogen and slowly stirring, the polymerization flask was heated to 75°C in a water bath and maintained at that temperature. 9 parts of ammonium persulfate was dissolved in 43 parts of ion-exchanged water, and the solution was added to a polymerization flask using a quantitative pump. After the emulsion was added dropwise via a metering pump over 20 minutes, the emulsion was added dropwise via a metering pump over 200 minutes. Thereafter, the polymerization flask was kept at 75° C. for 3 hours with continued stirring, and then returned to room temperature (25° C.) to complete the first stage polymerization. This resulted in a resin containing styrene-based resin particles, with the resin particles having a volume average particle size (D50v) of 190 nm, a glass transition temperature of 53°C, and a weight average A styrene-based resin particle dispersion (B1) having a molecular weight of 33,000 and a weight average molecular weight of 15,000 as determined by GPC (UV detection), and having a solid content of 40% by mass was obtained by adding ion-exchanged water.

[0223] [Preparation of release agent dispersion (A1)] Fischer-Tropsch wax: 270 parts (Manufactured by Nippon Seiro Co., Ltd., Product name: FNP-0090, Melting temperature = 90°C) Anionic surfactant: 1.0 parts (NEOGEN RK, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) Ion-exchanged water: 400 parts The above components were mixed and heated to 95°C, dispersed using a homogenizer (Ultra Turrax T50, manufactured by IKA), and then dispersed for 360 minutes using a Manton-Gaulin high pressure homogenizer (Gaulin), to prepare a release agent dispersion (A1) (solid content: 20% by mass) in which a release agent having a volume average particle size of 0.23 µm was dispersed.

[0224] [Preparation of Pressure Phase Change Particles (A1) and Developer (A1)] ·Composite resin particle dispersion (A1): 600 parts Release agent dispersion (A1): 8 parts Colloidal silica solution: 13 parts (Nissan Chemical Co., Ltd., Snowtex OS) Ion-exchanged water: 1000 parts Anionic surfactant: 1 part (Dow Chemical Company, Dowfax2A1)

[0225] The above components were placed in a 3-liter reaction vessel equipped with a thermometer, pH meter, and stirrer, and a 1.0% by mass aqueous solution of nitric acid was added at 25°C to adjust the pH to 3.0. The mixture was then dispersed at 5,000 rpm with a homogenizer (Ultra Turrax T50, manufactured by IKA Japan Co., Ltd.) while 4 parts of the prepared 10% by mass aqueous solution of polyaluminum chloride were added and dispersed for 6 minutes.

[0226] Thereafter, a mantle heater was placed in the reaction vessel, and the rotation speed of the stirrer was adjusted so that the slurry was sufficiently stirred. The temperature was raised at a rate of 0.2°C / min up to 40°C, and at a rate of 0.05°C / min after exceeding 40°C, and the particle size was measured every 10 minutes using a Multisizer II (aperture diameter: 50μm, manufactured by Coulter). When the volume average particle size reached 7.5μm, the temperature was maintained, and 115 parts of styrene-based resin particle dispersion (B1) were added over 5 minutes. After holding for 30 minutes after the end of the addition, the pH of the slurry was adjusted to 6.0 using a 1.0 mass% sodium hydroxide aqueous solution. Thereafter, the pH was adjusted to 6.0 every 5°C, and the temperature was raised to 96°C at a rate of 1°C / min, and maintained at 96°C. When the particle shape and surface properties were observed using an optical microscope and a field emission scanning electron microscope (FE-SEM), the coalescence of the particles was confirmed at the 2.0th hour, so the vessel was cooled to 30°C over 5 minutes with cooling water.

[0227] The cooled slurry was passed through a nylon mesh with a mesh size of 30 μm to remove coarse particles, and the slurry that passed through the mesh was filtered under reduced pressure with an aspirator. The solids remaining on the filter paper were crushed as finely as possible by hand, and then added to ion-exchanged water at a temperature of 30°C in an amount 10 times the solid content amount, and mixed by stirring for 30 minutes. The mixture was then filtered under reduced pressure with an aspirator, and the solids remaining on the filter paper were crushed as finely as possible by hand, and then added to ion-exchanged water at a temperature of 30°C in an amount 10 times the solid content amount, and then mixed by stirring for 30 minutes, after which the mixture was filtered under reduced pressure again with an aspirator, and the electrical conductivity of the filtrate was measured. This operation was repeated until the electrical conductivity of the filtrate was 10 μS / cm or less, and the solids were washed. The washed solid content was finely crushed with a wet-dry type granulator (Comil) and then vacuum dried for 36 hours in a dryer at 25°C to obtain base particles (A1). The obtained base particles (A1) had a volume average particle size of 8.1 µm, a weight average molecular weight of 126,000, and a number average molecular weight of 17,000.

[0228] Next, 1.5 parts of hydrophobic silica (RY50, manufactured by Nippon Aerosil Co., Ltd.) was added to 100 parts of the obtained base particles (A1), and mixed for 30 seconds at a rotation speed of 13000 rpm using a sample mill. After that, the mixture was sieved using a vibrating sieve with an opening of 45 μm to prepare pressure-induced phase transition particles (A1). The volume average particle diameter of the obtained pressure-induced phase transition particles (A1) was 8.4 μm.

[0229] When the thermal behavior of the pressure-induced phase transition particle (A1) sample was analyzed in the temperature range of -150°C to 100°C using a differential scanning calorimeter (Shimadzu Corporation, DSC-60A), the glass transition temperatures were observed at -60°C and 53°C.

[0230] The temperatures T1 and T2 of the pressure-induced phase transition particles (A1) were determined by the above-mentioned measurement method, and it was found that the pressure-induced phase transition particles (A1) satisfied the formula 1 "10° C.≦T1−T2".

[0231] When the cross section of the pressure-induced phase transition particle (A1) was observed with a scanning electron microscope (SEM), a sea-island structure was observed. The pressure-induced phase transition particle (A1) had a core part in which an island phase existed and a shell layer in which no island phase existed. The sea phase contained a styrene-based resin, and the island phase contained a (meth)acrylic ester-based resin. The average diameter of the island phase was determined by the above-mentioned measurement method and was found to be 250 nm.

[0232] For the pressure-induced phase transition particles (A1), the temperature difference (T1-T3), which is an index showing the ease with which the particles undergo phase transition due to pressure, was determined. Specifically, when temperatures T1 and T3 were measured using a flow tester (Shimadzu Corporation, CFT-500), the temperature T3 was 76°C and the temperature difference (T1-T3) was 17°C.

[0233] 8 parts of the pressure-induced phase transition particles (A1) and 100 parts of the resin-coated carrier described below were placed in a V-type blender and stirred for 20 minutes, and then sieved through a vibrating sieve with 212 μm openings to obtain developer (A1).

[0234] 14 parts of toluene, 2 parts of styrene-methyl methacrylate copolymer (mass ratio: 80 / 20, weight average molecular weight: 70,000), and 0.6 parts of MZ500 (zinc oxide, Titanium Industry) were mixed and stirred with a stirrer for 10 minutes to prepare a solution for forming a coating layer in which zinc oxide was dispersed. Next, this coating layer forming solution and 100 parts of ferrite particles (volume average particle diameter: 38 μm) were placed in a vacuum degassing kneader and stirred at 60°C for 30 minutes, and then the mixture was degassed under reduced pressure while being heated, and then dried to produce a resin-coated carrier.

[0235] <Preparation of toner and developer for forming image portion> [Crystalline polyester resin dispersion (A2)] A monomer component composed of 100 mol % dimethyl sebacate and 100 mol % nonanediol and 0.3 parts of dibutyltin oxide per 100 parts of the monomer component as a catalyst were placed in a heated and dried three-neck flask, and the air in the vessel was turned into an inert atmosphere with nitrogen gas by a pressure reduction operation, and the mixture was stirred and refluxed with a mechanical stirrer at 180°C for 4 hours.

[0236] The mixture was then gradually heated to 230°C under reduced pressure and stirred for 2 hours, and when it became viscous, it was air-cooled to stop the reaction, and crystalline polyester resin (A2) was synthesized. Molecular weight measurement (polystyrene equivalent) by gel permeation chromatography showed that the weight average molecular weight (Mw) of the obtained crystalline polyester resin (A2) was 15,300, the number average molecular weight (Mn) was 3,800, and the acid value was 13.5 mgKOH / g. Furthermore, when the melting point (Tm) of the crystalline polyester resin (A2) was measured using a differential scanning calorimeter (DSC), a clear endothermic peak was observed, and the endothermic peak temperature was 77.2°C.

[0237] Next, a resin particle dispersion liquid was prepared using the crystalline polyester resin (A2) as follows. Crystalline polyester resin (A2): 90 parts Ionic surfactant (Neogen RK, Daiichi Kogyo Seiyaku): 1.8 parts Ion-exchanged water: 210 parts The above ingredients were mixed and heated to 100°C, dispersed using a homogenizer (IKA Ultra Turrax T50), and then heated to 110°C using a pressure discharge type Gaulin homogenizer for 1 hour to obtain a crystalline polyester resin dispersion (A2) with a volume average particle size of 210 nm and a solid content of 30% by mass.

[0238] [Amorphous polyester resin dispersion (A2)] Bisphenol A propylene oxide adduct: 80 mol% Bisphenol A ethylene oxide 2 mole adduct: 20 mol% Terephthalic acid: 60 mol% Fumaric acid: 20 mol% Dodecenyl succinic anhydride: 20 mol% The monomer components were charged in the above ratio in a 5-liter flask equipped with a stirrer, a nitrogen inlet tube, a temperature sensor, and a distillation column, and the temperature was raised to 190°C over 1 hour. After confirming that the reaction system was stirred without unevenness, 1.2 parts of dibutyltin oxide was added to 100 parts of the monomer components. The temperature was then raised from the same temperature to 240°C over 6 hours while distilling off the water produced, and the dehydration condensation reaction was continued at 240°C for another 2 hours to obtain amorphous polyester resin (A2), which is a non-crystalline polyester resin with a glass transition temperature of 63°C, an acid value of 10.5 mgKOH / g, a weight average molecular weight of 17000, and a number average molecular weight of 4200.

[0239] Next, using the obtained amorphous polyester resin (A2), a resin particle dispersion was prepared as follows. Amorphous polyester resin (A2): 100 parts Ethyl acetate: 50 parts Ethyl acetate was added to a 5-liter separable flask, and then the resin components were gradually added, and the mixture was stirred with a three-one motor to completely dissolve the components and obtain an oil phase. A 10% by mass aqueous ammonia solution was gradually dripped into the stirred oil phase to a total of 2 parts with a dropper, and 230 parts of ion-exchanged water were gradually dripped at a rate of 10 ml / min to cause phase inversion emulsification, and the solvent was removed while the pressure was reduced with an evaporator to obtain an amorphous polyester resin dispersion (A2). The volume average particle size of the amorphous polyester resin particles in this dispersion was 120 nm, and the solid content was 30% by mass.

[0240] [Colorant particle dispersion (A1)] Carbon black (Cabot Corporation, Regal 330): 50 parts Anionic surfactant (NOF Corporation, Newlex R): 2 parts Ion-exchanged water: 198 parts The above components were mixed and pre-dispersed for 10 minutes using a homogenizer (Ultra Turrax, manufactured by IKA Corporation), and then dispersed for 15 minutes at a pressure of 245 MPa using an Ultimizer (opposed collision type wet grinder, manufactured by Sugino Machine Co., Ltd.) to obtain a colorant particle dispersion (A1) having a volume average particle size of 354 nm and a solid content of 20.0 mass %.

[0241] [Colorant particle dispersion (A2)] Blue pigment (copper phthalocyanine, CI Pigment blue 15:3, Dainichi Seika Chemicals): 50 parts Ionic surfactant (Neogen RK, Daiichi Kogyo Seiyaku): 5 parts Ion-exchanged water: 195 parts The above components were mixed and dispersed for 10 minutes using a homogenizer (Ultra Turrax, manufactured by IKA Corporation), and then dispersed for 15 minutes at a pressure of 245 MPa using an Ultimizer (opposed collision type wet grinder, manufactured by Sugino Machine Co., Ltd.) to obtain a colorant particle dispersion (A2) having a volume average particle size of 462 nm and a solid content of 20.0 mass %.

[0242] [Colorant particle dispersion (A3)] Magenta pigment (CI Pigment Red 122): 80 parts Anionic surfactant (Neogen SC, Daiichi Kogyo Seiyaku): 8 parts - Ion-exchanged water: 200 parts The above components were mixed and dissolved, dispersed for 10 minutes using a homogenizer (Ultra-Turrax T50, manufactured by IKA), and then irradiated with 28 kHz ultrasound for 10 minutes using an ultrasonic disperser to obtain a colorant particle dispersion (A3) having a volume average particle size of 132 nm and a solid content of 29.0 mass %.

[0243] [Colorant particle dispersion (A4)] Yellow pigment (5GX03, Clariant): 80 parts Anionic surfactant (Neogen SC, Daiichi Kogyo Seiyaku): 8 parts -Ion-exchanged water: 200 parts The above components were mixed and dissolved, dispersed for 10 minutes using a homogenizer (Ultra-Turrax T50, manufactured by IKA), and then irradiated with ultrasonic waves at 28 kHz for 20 minutes using an ultrasonic disperser to obtain a colorant particle dispersion (A4) having a volume average particle size of 108 nm and a solid content of 29.0 mass %.

[0244] [Release agent particle dispersion (A2)] Olefin wax (melting point: 88°C): 90 parts Ionic surfactant (Neogen RK, Daiichi Kogyo Seiyaku): 1.8 parts Ion-exchanged water: 210 parts The above ingredients were mixed and heated to 100°C, and dispersed using a homogenizer (IKA Ultra Turrax T50). The mixture was then heated to 110°C using a pressure discharge Gaulin homogenizer and dispersed for 1 hour to obtain a release agent particle dispersion (A2) having a volume average particle size of 180 nm and a solid content of 30% by mass.

[0245] [Preparation of black toner particles (A1)] Amorphous polyester resin dispersion (A2): 166 parts Crystalline polyester resin dispersion (A2): 50 parts Colorant particle dispersion (A1): 25 parts Release agent particle dispersion (A2): 40 parts The above was mixed and dispersed in a round stainless steel flask using a homogenizer (Ultra Turrax T50). Next, 0.20 parts of polyaluminum chloride was added to this, and the dispersion operation was continued using the Ultra Turrax T50. The flask was heated to 48°C with stirring in a heating oil bath. After maintaining at 48°C for 60 minutes, 60 parts of amorphous polyester resin dispersion (A2) were added little by little. After that, the pH of the system was adjusted to 8.0 with a 0.5 mol / l aqueous sodium hydroxide solution, the stainless steel flask was sealed, and the mixture was heated to 90°C with stirring using a magnetic seal, and maintained for 3 hours.

[0246] After the reaction was completed, the mixture was cooled, filtered, washed with ion-exchanged water, and then subjected to solid-liquid separation by Nutsche suction filtration. The mixture was then redispersed in 1 liter of ion-exchanged water at 40°C, stirred at 300 rpm for 15 minutes, and washed. This was repeated five more times, and when the pH of the filtrate reached 7.5 and the electrical conductivity reached 7.0 μS / cm, solid-liquid separation was performed using No. 5A filter paper by Nutsche suction filtration. Next, vacuum drying was continued for 12 hours to obtain black toner particles (A1). When the particle size of the black toner particles (A1) was measured by Multisizer II, the volume average particle size D50 was 6.4 μm and the volume particle size distribution index GSDv was 1.21.

[0247] [Preparation of black toner (A1)] 100 parts of black toner particles (A1), 0.8 parts of decylsilane-treated hydrophobic titania having an average particle diameter of 15 nm, and 1.3 parts of hydrophobic silica (NY50, manufactured by Nippon Aerosil Co., Ltd.) having an average particle diameter of 30 nm were mixed together, and the mixture was mixed for 10 minutes at a peripheral speed of 32 m / s using a Henschel mixer. After that, coarse particles were removed using a 45 μm mesh sieve, and black toner (A1) was obtained.

[0248] [Preparation of developer (C1)] Ferrite particles (volume average particle size: 50 μm, volume resistivity: 108 Ω cm): 100 parts Toluene: 14 parts Perfluorooctylethyl acrylate / methyl methacrylate copolymer (copolymerization ratio 40 / 60, Mw: 50,000): 1.6 parts Carbon black (VXC-72, manufactured by Cabot Corporation): 0.12 parts Crosslinked melamine resin particles (number average particle size: 0.3 μm): 0.3 parts The above components except for the ferrite particles were mixed and dispersed with a stirrer for 10 minutes to prepare a coating liquid. This coating liquid and the ferrite particles were placed in a vacuum degassing kneader and stirred at 60°C for 30 minutes, and then the pressure was reduced to remove the toluene, forming a resin coating on the surface of the ferrite particles to produce a carrier (A2).

[0249] 94 parts of the carrier (A2) and 6 parts of the black toner (A1) were mixed and stirred for 20 minutes at 40 rpm using a V-blender, and the mixture was sieved through a sieve having 177 μm mesh to prepare a developer (C1).

[0250] [Preparation of cyan toner particles (A2), cyan toner (A2), and developer (C2)] Cyan toner particles (A2) were obtained in the same manner as in the preparation of black toner particles (A1), except that 20 parts of colorant particle dispersion (A2) was used instead of colorant particle dispersion (A1). The volume average particle diameter D50 of the obtained toner particles was 7.2 μm, and the volume particle size distribution index was 1.19. Cyan toner (A2) was obtained in the same manner as black toner (A1), except that cyan toner particles (A2) were used instead of black toner particles (A1). A developer (C2) was obtained in the same manner as the developer (C1), except that the cyan toner (A2) was used instead of the black toner (A1).

[0251] [Preparation of Magenta Toner Particles (A3), Magenta Toner (A3), and Developer (C3)] Magenta toner particles (A3) were obtained in the same manner as in the preparation of black toner particles (A1), except that 25 parts of colorant particle dispersion (A3) was used instead of colorant particle dispersion (A1). The volume average particle diameter D50 of the obtained toner particles was 6.8 μm, and the volume particle size distribution index was 1.22. A magenta toner (A3) was obtained in the same manner as for the black toner (A1), except that the magenta toner particles (A3) were used instead of the black toner particles (A1). A developer (C3) was obtained in the same manner as the developer (C1), except that the magenta toner (A3) was used instead of the black toner (A1).

[0252] [Preparation of Yellow Toner Particles (A4), Yellow Toner (A4), and Developer (C4)] Yellow toner particles (A4) were obtained in the same manner as in the preparation of black toner particles (A1), except that 25 parts of colorant particle dispersion (A4) was used instead of colorant particle dispersion (A1). The volume average particle diameter D50 of the obtained toner particles was 7.4 μm, and the volume particle size distribution index was 1.19. Yellow toner (A4) was obtained in the same manner as black toner (A1), except that yellow toner particles (A4) were used instead of black toner particles (A1). A developer (C4) was obtained in the same manner as the developer (C1), except that the yellow toner (A4) was used instead of the black toner (A1).

[0253] <Creating pressure-bonded printed matter> [Laminated print (A1)] Developer (A1) containing pressure phase transition particles was supplied to a developing device of a modified Color1000 Press manufactured by Fuji Xerox Co., Ltd., which was filled with developers (C1) to (C4) for forming black, cyan, magenta, and yellow images.

[0254] Recording paper (OK Prince fine paper, manufactured by Oji Paper Co., Ltd.) was set as the recording medium, and the recording paper was prepared so that it could be folded in a Z-fold and laminated to produce a printed matter (laminated postcard) as follows, with the sides on both sides on which the image area and the pressure phase transition layer were formed being the laminated sides. The developer (A1) containing pressure-induced phase transition particles was contained in the developing machine located on the outermost surface of the image, and the image area and the pressure-induced phase transition layer were output simultaneously using an electrophotographic image forming apparatus in which the developers (C1) to (C4) were contained in the developing machines for each color. The pressure-induced phase transition layer was output on the pressure-bonded side of the pressure-bonded postcard, and only the toner for forming the image area was output on the areas that would become the address side and back side. The thickness of the pressure phase transition layer formed on the image area was adjusted so that the relationship with the thickness of the image area satisfied the relationship of formula 1 shown in Table 1.

[0255] Next, the recording paper was folded in a Z-fold, with the side on which the image area and the pressure phase transition layer were formed as the pressing surface, and pressed using a modified PRESSELE LEADA pressure sealer (manufactured by Toppan Forms Co., Ltd.) to produce a pressed print (A1).

[0256] [Lamination Printed Matter (A2)~(A19) , (A27), and (A28) ] Except for changing the conditions shown in Table 1, the pressure-bonded prints (A2) to (A19) were produced in the same manner as the pressure-bonded print (A1).

[0257] <Evaluation> The difference in pressure between the front pressure-bonded surface and the back pressure-bonded surface of each of the pressure-bonded printed products that had been folded in a Z-shape was evaluated as follows. Pressure difference less than 0.5: Break occurs × Pressure difference of 0.5 or more Breakage occurs

[0258] [Table 1]

[0259] From the above results, it can be seen that in this embodiment, the difference in bonding force between the front and back bonding surfaces of each bonded printed matter bonded by Z-folding is smaller than in the comparative example, and the variation in bonding force of the bonding surfaces is reduced.

[0260] Example B <Preparation of Dispersion Containing Styrene-Based Resin Particles> [Preparation of styrene-based resin particle dispersion (St1)] Styrene: 390 parts n-Butyl acrylate: 100 parts Acrylic acid: 10 parts Dodecanethiol: 7.5 parts The above materials were mixed and dissolved to prepare a monomer solution. 8 parts of anionic surfactant (Dowfax2A1, manufactured by Dow Chemical Company) was dissolved in 205 parts of ion-exchanged water, and the monomer solution was added thereto and dispersed and emulsified to obtain an emulsion. 2.2 parts of anionic surfactant (Dowfax2A1, manufactured by The Dow Chemical Company) was dissolved in 462 parts of ion-exchanged water, and the solution was charged into a polymerization flask equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, and the mixture was heated to 73°C with stirring and maintained at that temperature. 3 parts of ammonium persulfate was dissolved in 21 parts of ion-exchanged water and added dropwise to the polymerization flask via a metering pump over 15 minutes, and then the emulsion was added dropwise to the solution via a metering pump over 160 minutes. The polymerization flask was then maintained at 75° C. for 3 hours with continued slow stirring, and then allowed to cool to room temperature (25° C.). This resulted in a styrene-based resin particle dispersion (St1) containing styrene-based resin particles, with a volume average particle size (D50v) of 174 nm, a weight average molecular weight of 49 k by GPC (UV detection), a glass transition temperature of 54°C, and a solid content of 42 mass%.

[0261] The styrene-based resin particle dispersion (St1) was dried to extract the styrene-based resin particles, and the thermal behavior was analyzed in the temperature range of -100°C to 100°C using a differential scanning calorimeter (Shimadzu Corporation, DSC-60A), and one glass transition temperature was observed. Table 2 shows the glass transition temperatures.

[0262] [Preparation of styrene-based resin particle dispersions (St2) to (St13)] In the same manner as in the preparation of the styrene-based resin particle dispersion liquid (St1), except that the monomers were changed as shown in Table 2, styrene-based resin particle dispersion liquids (St2) to (St13) were prepared.

[0263] In Table 2, the monomers are represented by the following abbreviations. Styrene: St, n-Butyl acrylate: BA, 2-Ethylhexyl acrylate: 2EHA, Ethyl acrylate: EA, 4-Hydroxybutyl acrylate: 4HBA, Acrylic acid: AA, Methacrylic acid: MAA, 2-Carboxyethyl acrylate: CEA

[0264] [Table 2]

[0265] <Preparation of Dispersion Containing Composite Resin Particles> [Preparation of composite resin particle dispersion (M1)] Styrene-based resin particle dispersion (St1): 1,190 parts (solids: 500 parts) 2-Ethylhexyl acrylate: 250 parts -n-Butyl acrylate: 250 parts Ion-exchanged water: 982 parts The above materials were charged into a polymerization flask and stirred at 25°C for 1 hour, then heated to 70°C. 2.5 parts of ammonium persulfate was dissolved in 75 parts of ion-exchanged water, and the solution was added dropwise to the polymerization flask over 60 minutes via a metering pump. The polymerization flask was then maintained at 70° C. for 3 hours with continued slow stirring, and then allowed to cool to room temperature (25° C.). This resulted in a composite resin particle dispersion (M1) containing composite resin particles, the resin particles having a volume average particle size (D50v) of 219 nm, a weight average molecular weight by GPC (UV detection) of 219 k, and a solid content of 32 mass %.

[0266] The composite resin particle dispersion (M1) was dried to take out the composite resin particles, and the thermal behavior was analyzed in the temperature range of -150°C to 100°C using a differential scanning calorimeter (Shimadzu Corporation, DSC-60A). Two glass transition temperatures were observed. The glass transition temperatures are shown in Table 3.

[0267] [Preparation of Composite Resin Particle Dispersions (M2) to (M21)] Composite resin particle dispersions (M2) to (M21) were prepared in the same manner as in the preparation of the composite resin particle dispersion (M1), except that the styrene-based resin particle dispersion (St1) was changed as shown in Table 3, or the polymerization components of the (meth)acrylic ester-based resin were changed as shown in Table 3.

[0268] [Preparation of Composite Resin Particle Dispersions (M22) to (M27)] Composite resin particle dispersions (M22) to (M27) were prepared in the same manner as in the preparation of composite resin particle dispersion (M1), except that the amounts of 2-ethylhexyl acrylate and n-butyl acrylate used were adjusted.

[0269] In Table 3, the monomers are represented by the following abbreviations. Styrene: St, n-Butyl acrylate: BA, 2-Ethylhexyl acrylate: 2EHA, Ethyl acrylate: EA, 4-Hydroxybutyl acrylate: 4HBA, Acrylic acid: AA, Methacrylic acid: MAA, 2-Carboxyethyl acrylate: CEA, Hexyl acrylate: HA, Propyl acrylate: PA

[0270] [Table 3]

[0271] <Preparation of pressure phase transition particles> [Preparation of Pressure-Resistance Phase Change Particles (1) and Developer (1)] ·Composite resin particle dispersion (M1): 504 parts Ion-exchanged water: 710 parts Anionic surfactant (Dow Chemical Company, Dowfax2A1): 1 part

[0272] The above materials were placed in a reaction vessel equipped with a thermometer and a pH meter, and a 1.0% by mass nitric acid aqueous solution was added at a temperature of 25°C to adjust the pH to 3.0. Then, 23 parts of a 2.0% by mass aluminum sulfate aqueous solution were added while dispersing at a rotation speed of 5000 rpm with a homogenizer (IKA, Ultra Turrax T50). Next, a stirrer and a mantle heater were installed in the reaction vessel, and the temperature was raised at a rate of 0.2°C / min up to 40°C, and at a rate of 0.05°C / min after exceeding 40°C, and the particle size was measured every 10 minutes with a Multisizer II (aperture diameter 50 μm, Beckman Coulter). When the volume average particle size reached 5.0 μm, the temperature was maintained, and 170 parts of a styrene-based resin particle dispersion (St1) was added over 5 minutes. After the addition was completed, the mixture was held at 50°C for 30 minutes, and then a 1.0% by mass sodium hydroxide aqueous solution was added to adjust the pH of the slurry to 6.0. Next, the temperature was increased to 90°C at a rate of 1°C / min while adjusting the pH to 6.0 every 5°C, and then maintained at 90°C. When the particle shape and surface properties were observed using an optical microscope and a field emission scanning electron microscope (FE-SEM), coalescence of the particles was confirmed after 10 hours, so the container was cooled to 30°C over 5 minutes with cooling water.

[0273] The cooled slurry was passed through a nylon mesh with a mesh size of 15 μm to remove coarse particles, and the slurry that passed through the mesh was filtered under reduced pressure with an aspirator. The solids remaining on the filter paper were crushed as finely as possible by hand, and then added to ion-exchanged water (temperature 30°C) with 10 times the amount of solids, and stirred for 30 minutes. Next, the mixture was filtered under reduced pressure with an aspirator, and the solids remaining on the filter paper were crushed as finely as possible by hand, and then added to ion-exchanged water (temperature 30°C) with 10 times the amount of solids, and then stirred for 30 minutes, and then filtered under reduced pressure again with an aspirator, and the electrical conductivity of the filtrate was measured. This operation was repeated until the electrical conductivity of the filtrate was 10 μS / cm or less, and the solids were washed.

[0274] The washed solid content was crushed finely with a wet-dry type granulator (Comil) and vacuum-dried in an oven at 25° C. for 36 hours to obtain base particles (1). The base particles (1) had a volume average particle size of 8.0 μm.

[0275] 100 parts of the base particles (1) and 1.5 parts of hydrophobic silica (RY50, manufactured by Nippon Aerosil Co., Ltd.) were mixed and mixed for 30 seconds at a rotation speed of 13,000 rpm using a sample mill. The mixture was sieved using a vibrating sieve with 45 μm openings to obtain pressure-induced phase transition particles (1).

[0276] When the thermal behavior of the pressure phase transition particle (1) sample was analyzed in the temperature range of -150°C to 100°C using a differential scanning calorimeter (Shimadzu Corporation, DSC-60A), two glass transition temperatures were observed. The glass transition temperatures are shown in Table 4.

[0277] The temperatures T1 and T2 of the pressure-induced phase transition particles (1) were determined by the above-mentioned measurement method, and it was found that the pressure-induced phase transition particles (1) satisfied the formula 1 "10° C.≦T1−T2".

[0278] When the cross section of the pressure-induced phase transition particle (1) was observed with a scanning electron microscope (SEM), a sea-island structure was observed. The pressure-induced phase transition particle (1) had a core portion in which an island phase existed and a shell layer in which no island phase existed. The sea phase contained a styrene-based resin, and the island phase contained a (meth)acrylic ester-based resin. The average diameter of the island phase was determined by the measurement method described above. Table 4 shows the average diameter of the island phase.

[0279] 10 parts of the pressure-sensitive phase transition particles (1) and 100 parts of the resin-coated carrier described below were placed in a V-type blender and stirred for 20 minutes, and then sieved through a vibrating sieve with 212 μm openings to obtain developer (1).

[0280] Mn-Mg-Sr ferrite particles (average particle size 40 μm): 100 parts Toluene: 14 parts Polymethylmethacrylate: 2 parts Carbon black (VXC72: manufactured by Cabot): 0.12 parts The above materials except for the ferrite particles were mixed with glass beads (diameter 1 mm, same amount as toluene) and stirred for 30 minutes at a rotation speed of 1200 rpm using a sand mill manufactured by Kansai Paint Co., Ltd. to obtain a dispersion liquid. The dispersion liquid and the ferrite particles were placed in a vacuum degassing kneader, and dried under reduced pressure while stirring to obtain a resin-coated carrier.

[0281] [Preparation of Pressure-Resistance Phase Change Particles (2) to (27) and Developers (2) to (27)] Pressure-induced phase transition particles (2) to (27) and developers (2) to (27) were prepared in the same manner as in the preparation of pressure-induced phase transition particles (1), except that the composite resin particle dispersion and the styrene-based resin particle dispersion were changed as shown in Table 4.

[0282] When the temperatures T1 and T2 of the pressure-induced phase transition particles (2) to (27) were determined by the above-mentioned measurement method, all of the pressure-induced phase transition particles (2) to (27) satisfied the formula 1 "10°C≦T1-T2".

[0283] [Evaluation of pressure-responsive phase transition] The temperature difference (T1-T3), which is an index showing the ease with which particles undergo phase transition under pressure, was determined. Using each particle as a sample, the temperatures T1 and T3 were measured using a flow tester (Shimadzu Corporation, CFT-500), and the temperature difference (T1-T3) was calculated. Table 4 shows the temperature difference (T1-T3).

[0284] [Evaluation of crimping ability] As a printing device, an apparatus shown in Fig. 3 was prepared. That is, a printing device was prepared that was equipped with a 5-tandem type intermediate transfer type printing means that simultaneously forms an image area on a recording medium and applies pressure phase transition particles, and a pressing means having a folding device and a pressure device. Pressure phase transition particles (or comparative particles), yellow toner, magenta toner, cyan toner, and black toner were placed in five developing units of the printing means. The yellow toner, magenta toner, cyan toner, and black toner were commercially available products manufactured by Fuji Xerox Co., Ltd. As a recording medium, postcard paper V424 manufactured by Fuji Xerox was prepared. The image portion formed on the postcard paper was an image with an area density of 30% that contained a mixture of black characters and a full-color photographic image, and was formed on one side of the postcard paper. The amount of pressure-induced phase transition particles (or comparative particles) applied to the image forming area on the image forming surface of the postcard paper was 3 g / m 2 It was decided. The folding device was a device that folds postcard paper in half so that the image forming surface was on the inside. The pressure in the pressurizing device was set to 90 MPa. Using the above-mentioned device and conditions, ten postcards were continuously produced, each folded in half with the image-formed surface facing inward and with the image-formed surfaces fixed together. The tenth postcard was cut in the long direction to a width of 15 mm to prepare a rectangular test piece, and a 90-degree peel test was performed. The peel speed for the 90-degree peel test was 20 mm / min, and the load (N) was collected at 0.4 mm intervals from 10 mm to 50 mm after the start of the measurement, and the average was calculated. The load (N) for the three test pieces was also averaged. The load (N) required for peeling was classified as follows. The results are shown in Table 4.

[0285] A: 0.8N or more B: 0.6N or more, less than 0.8N C: 0.4N or more, less than 0.6N D: 0.2N or more, less than 0.4N E: Less than 0.2N

[0286] [Table 4] [Explanation of symbols]

[0287] 500 Printing means 516 Pressure Phase Transition Particles 516A Pressure Phase Transition Particle Region 518 Particle Applicator 518A Supply Roll 520, 520Y, 520M, 520C, 520K Inkjet Printing Heads 564 Fixing device 564A Heating Roll 564B Pressure Roll 200 Crimping means 220 Folding device 230 Pressurizing device 231, 232 Pressure roll P Recording medium P1 Recording medium after granting P2 Laminate P3 Printed material

[0288] 300 Printing means 1T, 1Y, 1M, 1C, 1K photoconductor 2T, 2Y, 2M, 2C, 2K Charging roll (an example of charging means) 3T, 3Y, 3M, 3C, 3K exposure equipment (an example of electrostatic image forming means) 4T, 4Y, 4M, 4C, 4K developing device (an example of developing means) 5T, 5Y, 5M, 5C, 5K Primary transfer roll (an example of a primary transfer means) 6T, 6Y, 6M, 6C, 6K Photoconductor cleaning device (an example of a cleaning means) 8T, 8Y, 8M, 8C, 8K cartridges 10T, 10Y, 10M, 10C, 10K units 20 Intermediate transfer belt (an example of an intermediate transfer body) 21 Intermediate transfer body cleaning device 22 Driving Roll 23 Support roll 24 Opposing Roll 26 Secondary transfer roll (an example of a secondary transfer means) 28 Heating device (an example of particle heating means) P Recording medium P4 Post-application recording medium P5 Laminate P6 Printed matter

Claims

1. The recording medium is folded and pressed onto the surface on which the image area and the pressure phase transition layer are formed, or the recording medium and another recording medium are stacked and pressed onto the surface on which the image area and the pressure phase transition layer are formed, and the surface on which the image area and the pressure phase transition layer are formed is used as a pressing surface. the pressure phase transition layer is formed on at least a portion of the image area and also on at least a portion of the non-image area on the pressure-bonding surface of the recording medium; an average thickness of the pressure-induced phase change layer formed on the image area of ​​the pressure-bonding surface of the recording medium is greater than an average thickness of the pressure-induced phase change layer formed on the non-image area; printed matter.

2. 2. The printed matter according to claim 1, wherein the thickness of the pressure phase transition layer formed on the image area increases as the thickness of the image area increases.

3. the average thickness of the pressure phase transition layer formed on the image area is 0.5 μm or more and 5.0 μm or less; The average thickness of the image area is more than 0 μm and 5.0 μm or less, The printed matter according to claim 2, further comprising: when the thickness BR of the image portion is 0.5 μm or less, the following formulae (1) to (3) are satisfied: Formula (1): AR=X1×BR+Y1 (Formula 1) Formula (2): 2≦X1≦10 Formula (3): 0.5≦Y1≦2 (In formula (1), AR represents the thickness (μm) of the pressure phase transition layer formed on the image area, and BR represents the thickness (μm) of the image area. However, the thicknesses represented by AR and BR are the thickness of the pressure phase transition layer directly above the image area and the thickness of the image area directly below the pressure phase transition layer from which the thickness was determined.)

4. 4. The printed matter according to claim 1, wherein the pressure phase transition layer formed on the image area has a coverage of 60% or more and 100% or less.

5. The printed matter according to claim 4 , wherein the coverage of the pressure phase transition layer formed in the non-image area is 10% or more and 60% or less.

6. The printed matter according to any one of claims 1 to 5, wherein the image portion is a toner image portion.

7. The pressure-induced phase transition layer comprises a styrene-based resin containing styrene and other vinyl monomers as polymerization components, and a (meth)acrylic acid ester-based resin containing at least two types of (meth)acrylic acid esters as polymerization components, the mass ratio of the (meth)acrylic acid esters to the total polymerization components being 90 mass % or more, and has at least two glass transition temperatures, and the difference between the lowest glass transition temperature and the highest glass transition temperature among the glass transition temperatures exhibited by the pressure-induced phase transition layer is 30° C. or more.

8. 8. The printed matter according to claim 7, wherein the mass ratio of styrene in all the polymer components of the styrene-based resin is 60 mass % or more and 95 mass % or less.

9. The printed matter according to claim 7 or 8, wherein the mass ratio of the two (meth)acrylic esters having the largest mass ratios among the at least two (meth)acrylic esters contained as polymerization components in the (meth)acrylic ester-based resin is 80:20 to 20:

80.

10. a pressure-induced phase transition particle applying step of applying pressure-induced phase transition particles onto the recording medium on which the image area is formed; a fixing step of fixing at least the pressure-induced phase change particles onto the recording medium to form a pressure-induced phase change layer; a pressure bonding step of folding the recording medium and pressure bonding the recording medium with the surface on which the image portion and the pressure phase transition layer are formed being a pressure bonding surface, or of stacking the recording medium and another recording medium and pressure bonding the recording medium and another recording medium with the surface on which the image portion and the pressure phase transition layer are formed being a pressure bonding surface; having The method for producing a printed matter according to any one of claims 1 to 9, wherein an amount of the pressure-induced phase transition particles applied to the image area is greater than an amount of the pressure-induced phase transition particles applied to a non-image area.

Citation Information

Patent Citations

  • Method for applying powder adhesive

    JP2008169284A

  • Powder adhesive

    JP2008170659A

  • Press-bonding printed material producing device, press-bonding printed material producing method and recording medium, on which press-bonding is recorded

    JP2008173831A

  • Printed matter and method for producing the same

    JP2013237201A

  • Adhesive material, sheet for producing press-bonding printed matter, method for producing sheet for producing press-bonding printed matter, press-bonding printed matter, method for producing press-bonding printed matter, and apparatus for producing press-bonding printed matter

    JP2019167471A